Optical film, polarizing plate, image display device, and optical film selection method
Patent Information
- Application Number
- JP2024107201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-09-30
- Filing Date
- 2024-07-03
- Publication Date
- 2025-03-13
AI Technical Summary
Existing optical films used in image display devices suffer from rainbow unevenness due to disturbances in the polarization state of linearly polarized light, which is not effectively addressed by existing techniques that either increase in-plane retardation or fail to eliminate the issue completely.
A biaxially stretched plastic film with an in-plane retardation of 2500 nm or less, featuring a low refractive index layer on its surface, is arranged to minimize the difference in reflectance between P and S waves, and the optical film is positioned to ensure specific angles between the absorption axis of the polarizer and the slow axis of the plastic film, reducing rainbow unevenness without increasing in-plane retardation.
The solution effectively suppresses rainbow unevenness when viewed with the naked eye by maintaining a low in-plane retardation and ensuring symmetrical distribution of light reflectance, enhancing the visual quality of image display devices.
Smart Images

Figure 00000044_0000 
Figure 00000044_0001 
Figure 00000044_0002
Abstract
Description
[Technical field]
[0001] The present disclosure relates to an optical film, a polarizing plate, an image display device, and a method for selecting an optical film. [Background technology]
[0002] Various optical plastic films are often used in optical members of image display devices, etc. For example, in an image display device having a polarizing plate on a display element, a plastic film is used to protect a polarizer constituting the polarizing plate.
[0003] Plastic films for image display devices to be used as polarizer protective films etc. preferably have excellent mechanical strength, and therefore stretched plastic films are preferably used as the plastic films for image display devices.
[0004] When a stretched plastic film is placed on a polarizer, there is a problem in that rainbow pattern unevenness is observed because the stretched plastic film disturbs the polarization state of linearly polarized light that has passed through the polarizer. To solve this problem, techniques such as those in Patent Documents 1 to 3 have been proposed. Hereinafter, in this specification, "rainbow pattern unevenness" may be referred to as "rainbow unevenness."
[0005] Patent Document 1 discloses a liquid crystal display device that can eliminate rainbow unevenness when an image is viewed through polarized sunglasses by using a specific white light source as the light source of the image display device, increasing the in-plane phase difference (retardation) of the stretched plastic film to 3,000 nm or more and 30,000 nm or less, and arranging the absorption axis of the polarizer and the slow axis of the stretched plastic film at approximately 45 degrees. However, the method of Patent Document 1 requires the use of a stretched plastic film with a large in-plane retardation. And stretched plastic films with a large in-plane retardation are usually uniaxially stretched, which has problems such as being prone to tearing in the stretching direction.
[0006] Patent Document 2 discloses a polarizing plate protective film having a specific range of reflectance at Brewster's angle. Patent Document 3 discloses a polarizing plate protective film having a difference of 20% or less between the reflectance of P waves and the reflectance of S waves at an incident angle of 50 degrees. The polarizing plate protective films of Patent Documents 2 and 3 aim to eliminate the visible rainbow unevenness by reducing the reflectance difference between P waves and S waves, which are the polarized components of light traveling from inside the image display device toward the viewer, without increasing the in-plane retardation of the film as in Patent Document 1.
[0007] Biaxially stretched plastic films are generally obtained by melt-extruding a plastic material to form a casting film, and then stretching the casting film in the machine direction and width direction. During this process, it is known that the orientation angle varies depending on the position in the width direction due to the so-called bowing phenomenon. It is generally said that the optical performance of a biaxially stretched plastic film is stable near the center in the width direction. However, with the polarizing plate protective films of Patent Documents 2 and 3, even when biaxially stretched plastic films obtained from near the center were used, rainbow unevenness could not be eliminated in some cases. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2011-107198 A [Patent Document 2] JP 2009-14886 A [Patent Document 3] JP 2010-204630 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present disclosure has an object to provide an optical film capable of suppressing rainbow unevenness when viewed with the naked eye without increasing the in-plane retardation, and a polarizing plate and an image display device using the optical film. Another object of the present disclosure is to provide a method for selecting an optical film capable of suppressing rainbow unevenness when viewed with the naked eye without increasing the in-plane retardation. [Means for solving the problem]
[0010] The present disclosure provides the following [1] to [5]. [1] An optical film having a low refractive index layer on a plastic film, The plastic film is a biaxially stretched plastic film having an in-plane retardation of 2500 nm or less, the low refractive index layer is located on the outermost surface of the optical film, An optical film having a region in which the difference between the maximum and minimum values of ΔEab is less than 17.0. Here, measurement 1 is carried out for laminate 1, and the L*, a*, and b* values in the L*a*b* color system are calculated. Measurement 2 is carried out for laminate 2, and the L*, a*, and b* values in the L*a*b* color system are calculated. Based on the results of measurement 1 and measurement 2, ΔEab is calculated under condition 1. <Measurement 1> A laminate 1 is prepared by laminating a polarizer and the optical film in this order on a surface light source. In the laminate 1, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is also arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees. Furthermore, the polarizer is also arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees. The surface light source of the laminate 1 is displayed as white, and the transmitted light emitted from the low refractive index layer side of the laminate 1 is measured at 1 degree intervals at elevation angles of 0 degrees or more and 80 degrees or less and azimuth angles of 0 degrees or more and 359 degrees or less, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows: <Measurement 2> A laminate 2 is prepared by laminating a polarizer on the same surface light source as in the measurement 1. The polarizer is arranged so that the absorption axis direction with respect to the surface light source is the same as in the measurement 1. The surface light source of the laminate 2 is displayed as white, and the transmitted light emitted from the polarizer side of the laminate 2 is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to approximately the same as that of Measurement 1 within the plane. <Condition 1> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1. ΔL* is converted into a grayscale from the maximum value to the minimum value in a specified gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L*, a*, and b* values of measurement 1 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2, and the L*, a*, and b* values of measurement 2 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2.
[0011] [2] A polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is the optical film described in [1]. [3] An image display device having a display element, and a polarizer and an optical film arranged on the light output side of the display element, wherein the optical film is the optical film described in [1], and is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees, and the surface of the optical film on the low refractive index layer side faces the opposite side to the display element.
[0012] [4] An image display device having a polarizer and an optical film on a light exit surface of a display element, the polarizer is disposed such that an angle between the direction of the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees; the polarizer and the biaxially stretched plastic film of the optical film are disposed so that an angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees; The optical film has a low refractive index layer on a biaxially stretched plastic film having an in-plane retardation of less than 2500 nm, the low refractive index layer being located on the outermost surface of the optical film, and the image display device has a region in which the difference between the maximum and minimum values of ΔEab is less than 17.0. Here, measurement 1A is performed on laminate 1A to calculate the L*, a*, and b* values in the L*a*b* color system. Measurement 2A is performed on laminate 2A to calculate the L*, a*, and b* values in the L*a*b* color system. Based on the results of measurements 1A and 2A, ΔEab is calculated under condition 1A. <Measurement 1A> A laminate 1A is prepared by laminating a polarizer and the optical film in this order on a display element. In the laminate 1A, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is also arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees. The display element of the laminate 1A is set to white, and the transmitted light emitted from the low refractive index layer side of the laminate 1A is measured at 1 degree intervals at elevation angles of 0 degrees or more and 80 degrees or less and azimuth angles of 0 degrees or more and 359 degrees or less, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows: <Measurement 2A> A laminate 2A was prepared by laminating a polarizer on the same display element as in the measurement 1A. The display element of the laminate 2A is set to white, and the transmitted light exiting from the polarizer side of the laminate 2A is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to approximately the same as that of measurement 1A within the plane. <Condition 1A> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2A from the L* value of measurement 1A. ΔL* is grayscaled from the maximum value to the minimum value in a specified gradation and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L*, a*, and b* values of Measurement 1A at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2, and the L*, a*, and b* values of Measurement 2A at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2.
[0013] [5] A method for selecting an optical film for an image display device, which comprises a polarizer and an optical film on a light exit surface of a display element, and which is arranged so that a direction of an absorption axis of the polarizer is parallel to a left-right direction or a top-bottom direction of the display element, comprising the steps of: A method for selecting an optical film for an image display device, comprising the steps of: an optical film X having a low refractive index layer on a biaxially stretched plastic film having an in-plane retardation of less than 2500 nm, the low refractive index layer being located on the outermost surface of the optical film X; and the optical film X having a region in which a difference between a maximum value and a minimum value of ΔEab is less than 17.0; and selecting an optical film X that satisfies the judgment condition as the optical film. Here, measurement 1B is performed on laminate 1B to calculate the L*, a*, and b* values in the L*a*b* color system. Measurement 2B is performed on laminate 2B to calculate the L*, a*, and b* values in the L*a*b* color system. Based on the results of measurements 1B and 2B, ΔEab is calculated under condition 1B. <Measurement 1B> A laminate 1B is prepared by laminating a polarizer and the optical film X in this order on a display element. In the laminate 1B, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film X is within 90 degrees ±5 degrees. The display element of the laminate 1B is set to white, and the transmitted light emitted from the low refractive index layer side of the laminate 1B is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows: <Measurement 2B> A laminate 2B was prepared by laminating a polarizer on the same display element as in the measurement 1B. The display element of the laminate 2B is set to white, and the transmitted light emerging from the polarizer side of the laminate 2B is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to be approximately the same as that of measurement 1B within the plane. <Condition 1B> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2B from the L* value of measurement 1B. ΔL* is grayscaled from the maximum value to the minimum value in a specified gradation and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. When ΔEab at each azimuth angle was calculated from the difference between the L*, a*, and b* values of measurement 1B at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2, and the L*, a*, and b* values of measurement 2B at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2, the difference between the maximum and minimum ΔEab values was less than 17.0. Effect of the Invention
[0014] The optical film of the present disclosure, and the polarizing plate and image display device using the optical film can suppress rainbow unevenness when viewed with the naked eye without increasing the in-plane retardation to 3000 nm or more. Furthermore, the method for selecting an optical film of the present disclosure can efficiently select an optical film that can suppress rainbow unevenness when viewed with the naked eye without increasing the in-plane retardation. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a cross-sectional view illustrating one embodiment of an optical film of the present disclosure. [Diagram 2] FIG. 2 is a cross-sectional view for explaining the arrangement in the thickness direction of the laminate 1 used in measurement 1. [Diagram 3] FIG. 11 is a cross-sectional view for explaining the arrangement in the thickness direction of the laminate 2 used in measurement 2. [Figure 4] The value (ΔL*) obtained by subtracting the L* value of measurement 2 from the L* value of measurement 1 is grayscaled to a specified grayscale level, and the figure is displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. [Diagram 5] FIG. 1 is a cross-sectional view showing one embodiment of a polarizing plate according to the present disclosure. [Figure 6] 1 is a cross-sectional view showing an embodiment of an image display device according to the present disclosure. [Figure 7] FIG. 2 is a plan view for explaining five measurement positions in a sample when an in-plane retardation or the like is calculated from the sample. [Figure 8] 1 is a cross-sectional photograph of an example of a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed. [Figure 9] 1 is a cross-sectional photograph of an example of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed. [Figure 10] FIG. 1 is a schematic diagram showing a continuous folding test. [Figure 11] A diagram for explaining [+αB-(-αB)], [+αG-(-αG)], and [+αR-(-αR)] under condition A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, embodiments of the present disclosure will be described. [Optical film] The optical film of the present disclosure has a low refractive index layer on a plastic film, the plastic film being a biaxially stretched plastic film having an in-plane retardation of 2500 nm or less, the low refractive index layer being located on the outermost surface of the optical film, and having a region in which the difference between the maximum and minimum values of ΔEab is less than 17.0. Here, measurement 1 is carried out for laminate 1, and the L*, a*, and b* values in the L*a*b* color system are calculated. Measurement 2 is carried out for laminate 2, and the L*, a*, and b* values in the L*a*b* color system are calculated. Based on the results of measurement 1 and measurement 2, ΔEab is calculated under condition 1.
[0017] <Measurement 1> A laminate 1 is prepared by laminating a polarizer and the optical film in this order on a surface light source. In the laminate 1, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees. The surface light source of the laminate 1 is displayed as white, and the transmitted light emitted from the low refractive index layer side of the laminate 1 is measured at 1 degree intervals at elevation angles of 0 degrees or more and 80 degrees or less and azimuth angles of 0 degrees or more and 359 degrees or less, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows:
[0018] <Measurement 2> A laminate 2 was prepared by laminating a polarizer on the same surface light source as in the above measurement 1. The surface light source of the laminate 2 is displayed as white, and the transmitted light emitted from the polarizer side of the laminate 2 is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to approximately the same as that of Measurement 1 within the plane. From the measurement results, the L* value, the a* value, and the b* value at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is the above-mentioned (α+β) / 2 are confirmed.
[0019] <Condition 1> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1. ΔL* is converted into a grayscale from the maximum value to the minimum value in a specified gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L*, a*, and b* values of measurement 1 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2, and the L*, a*, and b* values of measurement 2 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2.
[0020] In this specification, unless otherwise specified, Measurement 1, Measurement 2, and the measurements described later (in-plane retardation, retardation in the thickness direction, direction of the slow axis, surface roughness of the low refractive index layer, etc.) are performed in an atmosphere with a temperature of 23°C ± 5°C and a relative humidity of 40% RH or more and 65% RH or less. Furthermore, before each measurement, the measurement sample is exposed to the atmosphere for 30 minutes or more.
[0021] 1 is a cross-sectional view showing an embodiment of an optical film 100 of the present disclosure. As shown in FIG. 1, the optical film 100 of the present disclosure has a low refractive index layer 30 on a plastic film 10. The optical film 100 of the present disclosure may have layers other than the plastic film 10 and the low refractive index layer 30. Examples of layers other than the plastic film 10 and the low refractive index layer 30 include a hard coat layer, an antiglare layer, and a high refractive index layer. The optical film 100 in FIG. 1 has a hard coat layer 20 between the plastic film 10 and the low refractive index layer 30.
[0022] Regarding measurement 1: Measurement 1 can be carried out as follows (1-1) to (1-2). (1-1) A laminate 1 is prepared by laminating a polarizer and an optical film in this order on a surface light source. In the laminate 1, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is also arranged so that the angle between the direction of the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees. Furthermore, the polarizer is also arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees.
[0023] FIG. 2 is a cross-sectional view for explaining the arrangement in the thickness direction of the laminate 1 used in the above (1-1). The laminate 1(X) in FIG. 2 includes a surface light source 200, a polarizer 300, and an optical film 100 laminated with an adhesive layer 400 interposed therebetween. As shown in FIG. 2, the surface light source, the polarizer, and the optical film are preferably bonded together with an adhesive layer or the like interposed therebetween. The above-mentioned bonding may be performed by, for example, temporary bonding via a liquid such as water or a solvent, as long as the bonding is performed in appearance. The laminate 1 may also have an optically isotropic film. For example, an optically isotropic film may be provided as a polarizer protective film on one or both sides of the polarizer.
[0024] The adhesive layer used to prepare the laminate 1 and the laminate 2 described later preferably has a refractive index of 1.42 or more and 1.53 or less, and a thickness of 15 μm or more and 40 μm or less. The adhesive layer more preferably has a refractive index of 1.45 or more and 1.50 or less, and a thickness of 20 μm or more and 30 μm or less. If the refractive index and thickness of the adhesive layer are within the above ranges, it can be said that there is no substantial effect on ΔEab described later. In this specification, the refractive index is a dimensionless parameter. The adhesive layer used to prepare the laminate 1 and the laminate 2 described later preferably has substantially no internal haze. The adhesive layer may be a general-purpose adhesive layer such as a curing adhesive layer, a pressure-sensitive adhesive layer (a so-called pressure-sensitive adhesive layer), or a heat-sensitive adhesive layer (a heat seal layer).
[0025] In the above (1-1), the polarizer is disposed so that the absorption axis of the polarizer is approximately parallel to the left-right direction or the up-down direction of the surface light source. In this specification, approximately parallel means that the difference between the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees, preferably within ±3 degrees, and more preferably within ±1 degree. If the planar shape of a surface light source is rectangular or square, it is easy to determine the left-right or up-down direction. It is not necessary to distinguish between left-right and up-down. If the planar shape of the surface light source is a shape other than a rectangle or square (circle, triangle, etc.), draw a rectangle or square that has the largest area that does not extend beyond the outer frame shape of the surface light source, and determine the left-right or up-down directions based on the drawn rectangle or square. In the above (1-1), the polarizer is arranged so that the angle between the direction of the absorption axis and the left-right or up-down direction of the surface light source is within ±5 degrees, taking into consideration that polarizers on the light exit surface side of general-purpose image display devices are arranged in this manner.
[0026] In the above (1-1), the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film are arranged so as to be approximately perpendicular to each other. In this specification, approximately perpendicular means that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film is within 90 degrees ± 5 degrees, preferably within 90 degrees ± 3 degrees, and more preferably within 90 degrees ± 1 degree. The slow axis means the direction in the plane of the biaxially stretched plastic film in which the refractive index is the largest. When the direction of the slow axis is not uniform in the plane of the biaxially stretched plastic film, the direction of the slow axis of the biaxially stretched plastic film means the average direction of the slow axis in the plane of the biaxially stretched plastic film.
[0027] In the above (1-1), the polarizer preferably has a polarization degree of 99.00% or more and an average transmittance of 35% or more, more preferably a polarization degree of 99.90% or more and an average transmittance of 37% or more, and even more preferably a polarization degree of 99.95% or more and an average transmittance of 40% or more. In this specification, the average transmittance means the average of the spectral transmittance at a wavelength of 400 nm or more and 700 nm or less. The wavelength interval for measuring the average transmittance is 5 nm. The polarizer may have an optically isotropic film on one or both sides thereof. The polarizer and the optically isotropic film may be attached to each other via an adhesive layer.
[0028] The polarizer used in Measurement 1 and Measurement 2 may be a polarizer that is disposed in advance on the display element, or may be a polarizer that is separately prepared.
[0029] In the above (1-1), the surface light source is not particularly limited as long as it can display white. The light emitted from the surface light source passes through a polarizer and becomes linearly polarized light, and the linearly polarized light enters the optical film. The linearly polarized light that enters the optical film can be assumed to be light emitted from a display element of a general-purpose image display device and further passed through a viewer-side polarizer (linearly polarized light). The surface light source may be, for example, a general-purpose image display device such as a liquid crystal display device or an organic EL display device. However, when the image display device has a viewer-side polarizer on the display element, the viewer-side polarizer is excluded from the surface light source. This is because the viewer-side polarizer can be the polarizer of the laminate 1 and the laminate 2. When the surface light source is a liquid crystal display device, examples of the backlight of the liquid crystal display device include a backlight using quantum dots and a backlight using white light-emitting diodes. A laminate in which an optical film is disposed on an image display device having a viewing-side polarizer on a display element can be regarded as Laminate 1 used in Measurement 1 so long as it satisfies the other conditions of Measurement 1. Furthermore, an image display device having a viewing-side polarizer on a display element can be regarded as the laminate 2 used in Measurement 2 so long as the other conditions of Measurement 2 are satisfied.
[0030] (1-2) The surface light source of the laminate 1 is displayed as white, and the transmitted light emitted from the low refractive index layer side of the laminate 1 is measured at 1 degree intervals at elevation angles of 0 degrees or more and 80 degrees or less and azimuth angles of 0 degrees or more and 359 degrees or less, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows:
[0031] In the above (1-2), the measurement area is 1 mm 2 The reason for limiting the measurement area to 10 mm is that if the area is too small, it is difficult for people to recognize it with their eyes. 2 The reason for specifying the value below is to suppress the influence of the emission angle distribution of the surface light source, and also to take into consideration that if the area is too large, ΔEab will be averaged, making it difficult to correlate with the visual result. The maximum elevation angle is set to 80 degrees because generally, light emitted from an elevation angle exceeding 80 degrees is nearly parallel to the plane, making it difficult to detect the emitted light. In the above (1-2), the measurement area is 1 mm 2 More than 5mm 2 It is preferable that:
[0032] In the above (1-2), the distance between the laminate 1 and the transmitted light measuring device is preferably more than 0 mm and not more than 1.5 mm, more preferably 0.5 mm to 1.5 mm, and even more preferably 1.0 mm. This distance suppresses deformation of the laminate 1 due to the weight of the measuring device, and also suppresses the spread of the emitted light, making it easier to reduce measurement errors. Similarly, in the later-described (2-2), the distance between the laminate 2 and the transmitted light measuring device is preferably within the above range.
[0033] The measurements and analyses in (1-2) above, (2-2) below, and (3-1) to (3-4) below can be carried out using, for example, ELDIM's product name "EzContrast."
[0034] In this specification, the L* value, a* value, and b* value are based on the L*a*b* color system standardized by the International Commission on Illumination (CIE) in 1976. The L*a*b* color system is adopted in JIS Z8781-4:2013.
[0035] Regarding measurement 2: Measurement 2 can be carried out as follows (2-1) to (2-2).
[0036] (2-1) A laminate 2 is prepared by laminating a polarizer on the same surface light source as in the above-mentioned measurement 1. The polarizer is arranged so that the direction of the absorption axis with respect to the surface light source is the same as that in the above-mentioned measurement 1. The polarizer used in the measurement 2 is the same as that used in the measurement 1.
[0037] FIG. 3 is a cross-sectional view for explaining the arrangement in the thickness direction of the laminate 2 used in the above (2-1). In the laminate 2(Y) in Fig. 3, a surface light source 200 and a polarizer 300 are laminated via an adhesive layer 400. As shown in Fig. 3, the surface light source and the polarizer are preferably bonded together via an adhesive layer or the like. Note that the above-mentioned bonding only needs to be apparently bonded together, and may be temporary bonding via a liquid such as water or a solvent.
[0038] In the above (2-1), the polarizer is arranged so that the direction of the absorption axis with respect to the surface light source is the same as that in the above measurement 1. For example, when the polarizer is arranged so that the absorption axis direction is parallel to the left-right direction of the surface light source in measurement 1, the polarizer is arranged in the same manner in the above (2-1).
[0039] (2-2) The surface light source of the laminate 2 is displayed as white, and the transmitted light emitted from the polarizer side of the laminate 2 is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is approximately the same as that of measurement 1 within the plane.
[0040] In the above (2-2), the measurement area of the transmitted light being approximately the same in-plane as that of Measurement 1 means that when laminate 1 and laminate 2 are superimposed and viewed in a plane, the distance between the center of the measurement area of the transmitted light in Measurement 1 and the center of the measurement area of the transmitted light in Measurement 2 is within 0.5 mm, preferably within 0.3 mm, and more preferably within 0.1 mm.
[0041] As described in (1-1) above, the surface light source used in Measurement 1 and Measurement 2 is not particularly limited as long as it can display white, but in order to perform stable measurements, a surface light source in which the averages of the L* value, a* value, and b* value in the state of the laminate 2 indicate the following ranges (a1) to (a3) is preferred. In other words, in order to perform stable measurements, the averages of the L* value, a* value, and b* value in Measurement 2 preferably indicate the following ranges. (a1) The average L* value for all angles obtained in the measurement in (2-2) above is 95 or more and 105 or less. The average L* value for all angles is more preferably 95 or more and 100 or less. (a2) The average a* value for all angles obtained in the measurement in (2-2) above is −10 or more and 10 or less. The average a* value for all angles is more preferably −5 or more and 5 or less. (a3) The average b* value for all angles obtained in the measurement in (2-2) above is −10 or more and 10 or less. The average b* value for all angles is more preferably −5 or more and 5 or less.
[0042] Furthermore, in order to perform a more stable measurement, it is more preferable for the surface light source to have the variations (3σ) of the L* value, a* value, and b* value in the state of the laminate 2 to satisfy the following ranges (b1) to (b3). In other words, in order to perform a stable measurement, it is preferable for the variations (3σ) of the L* value, a* value, and b* value in measurement 2 to satisfy the following ranges. (b1) The variation (3σ) of the L* value across all angles obtained by the measurement in (2-2) above is not more than 120. The variation (3σ) of the L* value across all angles is more preferably not more than 115. (b2) The variation (3σ) of the absolute values of the a* values over all angles obtained in the measurement in (2-2) above is 15 or less. (b3) The variation (3σ) of the absolute values of the b* values for all angles obtained in the measurement in (2-2) above is 15 or less.
[0043] In order to more easily suppress rainbow unevenness, the surface light source preferably satisfies the following condition A. Satisfying condition A means that at least one of the full width at half maximum of the intensity peaks present in the blue wavelength region, the green wavelength region, and the red wavelength region is equal to or greater than a predetermined value (10 nm or greater). Figure 11 shows the [+α B -(-α B )], [+α G -(-α G )] and [+α R -(-α R 11 is a diagram for explaining the spectrum of a surface light source of a general-purpose organic EL element.
[0044] <Condition A> A first polarizer is placed on a surface light source, and the intensity of light L1 emitted vertically from the first polarizer side is measured at wavelength intervals of 1 nm. The blue wavelength range is 400 nm or more and less than 500 nm, the green wavelength range is 500 nm or more and less than 570 nm, and the red wavelength range is 570 nm or more and less than 780 nm. The maximum intensity of the blue wavelength range of L1 is B. max , the maximum intensity of the green wavelength region of L1 is G max , the maximum intensity of the red wavelength region of L1 is R max Let us assume that. B max Let L1λ be the wavelength that indicates B , G max Let L1λ be the wavelength that indicates G , R max Let L1λ be the wavelength that indicates R Let us assume that. B max A wavelength that exhibits an intensity of 1 / 2 or less of L1λ B The minimum wavelength located on the negative side of B , B max A wavelength that exhibits an intensity of 1 / 2 or less of L1λ B The minimum wavelength located on the positive side of B , G max A wavelength that exhibits an intensity of 1 / 2 or less of L1λ G The maximum wavelength located on the negative side of G , G max A wavelength that exhibits an intensity of 1 / 2 or less of L1λ G The minimum wavelength located on the positive side of G , R max A wavelength that exhibits an intensity of 1 / 2 or less of L1λ R The maximum wavelength located on the negative side of R , R max A wavelength that exhibits an intensity of 1 / 2 or less of L1λ R The maximum wavelength located on the positive side of R Let us assume that. [+α B -(-α B )], [+α G -(-α G )] and [+α R -(-α R)] is 10 nm or more.
[0045] In condition A, it is more preferable that two or more of [+αB-(-αB)], [+αG-(-αG)], and [+αR-(-αR)] are 10 nm or more, and it is even more preferable that all three are 10 nm or more.
[0046] Regarding condition 1: In condition 1, the difference between the maximum and minimum values of ΔEab calculated by the following procedure is calculated based on the L* value, a* value, and b* value obtained in the above-mentioned measurement 1 and measurement 2. The optical film of the present disclosure is required to have a region where the difference is less than 17.0. <Condition 1> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1. ΔL* is converted into a grayscale from the maximum value to the minimum value in a specified gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L*, a*, and b* values of measurement 1 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2, and the L*, a*, and b* values of measurement 2 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2.
[0047] ΔEab is what is called color difference. When the “L* value, a* value, and b* value” of measurement 1 and measurement 2 at a specific azimuth angle are defined as “L1*, a1*, and b1*” and “L2*, a2*, and b2*,” respectively, the color difference (ΔEab) at the specific azimuth angle can be expressed by the following formula. <Formula for color difference (ΔEab)> ΔEab={(L1*-L2*) 2+(a1*-a2*) 2 +(b1*-b2*) 2} 1 / 2
[0048] ΔEab in condition 1 can be calculated according to the following procedures (3-1) to (3-4) based on the L*, a*, and b* values obtained in measurements 1 and 2. That is, ΔEab in condition 1 specifies the color difference between a state with an optical film and a state without an optical film. This is to cancel the influence of the surface light source and provide a correlation with rainbow unevenness. "(L1* 2 +a1* 2 +b1* 2 ) 1 / 2 " has no correlation with the visibility of rainbow unevenness. This is thought to be because the L* value of the surface light source has a large effect.
[0049] (3-1) For all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1. ΔL* is converted into a grayscale from the maximum value to the minimum value in a specified gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angles are represented by concentric circles and the azimuth angles are represented by vertical and horizontal lines.
[0050] Figure 4 shows the maximum to minimum values of ΔL* in a grayscale with a specified gradation, and displays them in grayscale on a two-dimensional coordinate system with the elevation angle represented by concentric circles and the azimuth angle represented by vertical and horizontal lines. In other words, Figure 4 is the two-dimensional coordinate system of (3-1) above. In Figure 4, the closer to white the value, the larger the ΔL*. In Fig. 4, the center of the circular two-dimensional coordinate system indicates an elevation angle of 0 degrees (perpendicular to the surface light source), and the edge indicates the maximum elevation angle. Also, in Fig. 4, the direction to the right from the center indicates an azimuth angle of 0 degrees, the direction above from the center indicates an azimuth angle of 90 degrees, the direction to the left from the center indicates an azimuth angle of 180 degrees, and the direction below from the center indicates an azimuth angle of 270 degrees.
[0051] The gradation level in (3-1) above is usually the nth power of 2, and examples of this include 16 gradations, 32 gradations, 64 gradations, 128 gradations, and 256 gradations. The two-dimensional coordinates of the grayscale display in (3-1) above can be created, for example, using ELDIM's product name "EzContrast."
[0052] (3-2) It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Here, "substantially symmetrical" means that when the elevation angle and azimuth angle at the center of one region where ΔL* is distributed concentrically are defined as X1 and Y1, and the elevation angle and azimuth angle at the center of the other region where ΔL* is distributed concentrically are defined as X2 and Y2, the difference between X1 and X2 is ±3 degrees or less, and the absolute value of the difference between Y1 and Y2 is 180 degrees ±5 degrees or less. It is preferable that the difference between X1 and X2 is ±1 degree or less, and the absolute value of the difference between Y1 and Y2 is 180 degrees ±3 degrees or less.
[0053] In the two-dimensional coordinate system shown in FIG. 4, there are two regions in which ΔL* is distributed concentrically, and the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. It is believed that such concentric circles at symmetrical positions are formed by fluctuations in the reflectance of P waves and S waves due to the refractive index distribution in the measurement region (biaxially stretched plastic film has a high refractive index in the slow axis direction, so concentric circles are formed along the slow axis. In the case of Figure 4, the direction of the slow axis of the biaxially stretched plastic film is the left-right direction in Figure 4.) and changes in the optical distance of the low refractive index layer in the measurement region (the optical distance (the distance of transmitted light passing through the low refractive index layer) increases with distance from the measurement center). In other words, such concentric circles at symmetrical positions are normally formed in an optical film having a low refractive index layer on a biaxially stretched plastic film (measurement 1), and in the biaxially stretched plastic film alone (and the higher the in-plane retardation, the more likely it is that concentric circles will be formed at symmetrical positions). Furthermore, since measurement 2 contains only P waves or S waves and does not form the concentric circles as described above, the difference in the L* values (ΔL*) between measurements 1 and 2 maintains the concentric circles formed by the L* value in measurement 1 (ΔL*) because the influence of the light source is cancelled out, so the fluctuations in the reflectance of P waves and S waves become clearer and the concentric circles are also formed more clearly).
[0054] (3-3) Regarding the elevation angles located at the centers of the regions in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees.
[0055] In the above (3-3), the "elevation angle at the center of the area where ΔL* is distributed concentrically" can be determined, for example, by displaying two-dimensional coordinates on the software of the measuring device and selecting the center of the area where ΔL* is distributed concentrically (for example, by clicking the center of the area where ΔL* is distributed concentrically with the mouse).
[0056] (3-4) From the measurement results, calculate ΔEab at each azimuth angle from the difference between the L*, a*, and b* values of measurement 1 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2 and the L*, a*, and b* values of measurement 2 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2. Then, calculate the difference between the maximum and minimum values of ΔEab.
[0057] In the above (3-4), if a fraction occurs in (α+β) / 2, the value is rounded up. For example, if α is 30 degrees and β is 31 degrees, ΔEab is calculated from the L*, a*, and b* values at an azimuth angle between 0 degrees and 359 degrees when the elevation angle is 31 degrees.
[0058] (α+β) / 2 is preferably 50 degrees or less, more preferably 40 degrees or less, and even more preferably 30 degrees or less. By setting (α+β) / 2 to 50 degrees or less, the value of (α+β) / 2 moves away from the vicinity of the Brewster angle, making it easier to suppress fluctuations in the reflectance of P waves and S waves at angles around (α+β) / 2. There is no particular lower limit for (α+β) / 2, but it is preferably 5 degrees or more, more preferably 10 degrees or more, and even more preferably 15 degrees or more. By reducing the refractive index nz in the thickness direction of the biaxially stretched plastic film, it is possible to easily bring (α+β) / 2 into the above range.
[0059] The optical film of the present disclosure requires that the difference between the maximum and minimum values of ΔEab calculated at each azimuth angle (0 degrees or more and 359 degrees or less) is less than 17.0. A large difference means that a color is perceived as being strong at a specific azimuth angle. Therefore, when the difference is 17.0 or more, a color is perceived as being strong at the azimuth angle at which ΔEab shows the maximum value, and rainbow unevenness seen by the naked eye cannot be suppressed. The difference is preferably 16.0 or less, more preferably 15.0 or less, and even more preferably 14.0 or less. The lower limit of the difference is not particularly limited, but is usually about 3.0. The difference can be easily made less than 17.0 by using, for example, a biaxially stretched plastic film that satisfies condition 2 described below.
[0060] In condition 1, the reason for using the measured values with azimuth angles between 0 degrees and 359 degrees passing through (α + β) / 2 is that in the direction passing through (α + β) / 2, the bright and dark areas of the concentric circles are measured alternately (see Figure 4), and the difference between the maximum and minimum values of ΔEab is theoretically the largest. In addition, the present disclosure is characterized in that it uses the azimuth angle passing through the center of the concentric circle ((α+β) / 2) instead of the Brewster angle. The above-mentioned concentric circle of ΔL* is affected by the in-plane phase difference (the larger the in-plane phase difference, the smaller the concentric circle). On the other hand, the Brewster angle is governed by the refractive index and is not affected by the in-plane phase difference. Therefore, even if the "difference between the maximum and minimum values of ΔEab" calculated from the measurement value of the azimuth angle passing through the Brewster angle is small, it is difficult to reduce the "difference between the maximum and minimum values of ΔEab" calculated from the measurement value of the azimuth angle passing through (α+β) / 2. In other words, the present disclosure has a technical significance superior to Patent Documents 2 and 3 in that it is possible to suppress the visibility of rainbow unevenness by making the "difference between the maximum and minimum values of ΔEab" calculated from the measurement value of the azimuth angle passing through (α+β) / 2, rather than the Brewster angle, satisfy a predetermined condition. In addition, as described below, n x >n y ≧n z In the biaxially stretched plastic film that satisfies the above relationship, the phase difference in the oblique direction gradually decreases as it inclines along the direction of the slow axis, and becomes 0 nm near "(α+β) / 2". The present inventors have found that when the elevation angle is fixed to "(α+β) / 2" and the color is observed at an azimuth angle of 0 to 359 degrees, color unevenness similar to rainbow unevenness is strongly felt. Usually, rainbow unevenness is observed in a direction in which the phase difference has a predetermined value. However, when the elevation angle is fixed to "(α+β) / 2" and the observation is performed at an azimuth angle of 0 to 359 degrees, the oblique phase difference in the slow axis direction is 0 nm, which is completely different from normal observation. For this reason, in this specification, the color unevenness that is visually recognized at an elevation angle of "(α+β) / 2" and the azimuth angle of 0 to 359 degrees is sometimes referred to as "color distortion" to distinguish it from "rainbow unevenness".
[0061] In the optical film, the area in which the difference between the maximum and minimum values of ΔEab is less than 17.0 is preferably 50% or more, more preferably 70% or more, even more preferably 90% or more, and even more preferably 100%. Similarly, the area that satisfies various parameters other than the above difference (in-plane retardation, retardation in the thickness direction, condition 2, surface roughness of the low refractive index layer, etc.) is preferably 50% or more, more preferably 70% or more, even more preferably 90% or more, and even more preferably 100% in the optical film.
[0062] The maximum value of ΔEab calculated at each azimuth angle (0 degrees or more and 359 degrees or less) is preferably 16.0 or less, more preferably 15.0 or less, and even more preferably 14.0 or less. By setting the maximum value of ΔEab within the above range, it is possible to make rainbow spots less visible to the naked eye.
[0063] In the optical film of the present disclosure, when the Brewster angle for light in the entire visible light range incident on the optical film from the biaxially stretched plastic film side is defined as X degrees, it is preferable that the (α+β) / 2 and the X satisfy the following formula (A): X-(α+β) / 2≦20 degrees (A) The Brewster angle (X) can be calculated from the refractive indices of two materials using the following formula (B), where n1 is the refractive index on the incident side and n2 is the refractive index on the transmitting side. X=Arctan(n2 / n1) (B)
[0064] The optical film of the present disclosure can exhibit more remarkable effects when the Brewster angle is misaligned with the center of the concentric circle ((α+β) / 2). In other words, an optical film satisfying the above formula (A) is preferable in that it easily exhibits the effects of the present disclosure. X-(α+β) / 2 is more preferably equal to or greater than 30 degrees, and even more preferably equal to or greater than 35 degrees. The upper limit of X-(α+β) / 2 is not particularly limited, but is about 40 degrees.
[0065] <Plastic film> The plastic film is a biaxially oriented plastic film having an in-plane retardation of 2500 nm or less. By making it a biaxially stretched plastic film, the mechanical strength can be improved. In addition, by making the in-plane retardation of the biaxially stretched plastic film 2500 nm or less, the longitudinal and transverse stretching ratio can be kept within a moderate range, and the mechanical strength can be improved and the tear resistance can be improved. In addition, by making the in-plane retardation of the biaxially stretched plastic film 2500 nm or less, it can also contribute to making the biaxially stretched plastic film thinner.
[0066] In order to easily suppress rainbow unevenness, the in-plane retardation of the biaxially stretched plastic film is preferably 2000 nm or less, more preferably 1500 nm or less, more preferably 1400 nm or less, more preferably 1150 nm or less, more preferably 1000 nm or less, and more preferably 600 nm or less. When the thickness of the biaxially stretched plastic film is reduced to 10 μm or more and 50 μm or less, the in-plane retardation is preferably 1400 nm or less.
[0067] If the in-plane retardation of the biaxially stretched plastic film is too small, the mechanical strength may not be sufficient even after biaxial stretching. Therefore, the in-plane retardation of the biaxially stretched plastic film is preferably 20 nm or more, more preferably 100 nm or more, even more preferably 300 nm or more, and even more preferably 520 nm or more.
[0068] Preferred ranges of the in-plane retardation of the biaxially stretched plastic film are 20 nm or more and 2000 nm or less, 20 nm or more and 1500 nm or less, 20 nm or more and 1400 nm or less, 20 nm or more and 1150 nm or less, 20 nm or more and 1000 nm or less, 20 nm or more and 600 nm or less, 100 nm or more and 2000 nm or less, 100 nm or more and 1500 nm or less, 100 nm or more and 1400 nm or less, 100 nm or more and 1150 nm or less, 100 nm or more and 1000 nm or less, and 100 nm or less. and 600 nm or less, 300 nm or more and 2000 nm or less, 300 nm or more and 1500 nm or less, 300 nm or more and 1400 nm or less, 300 nm or more and 1150 nm or less, 300 nm or more and 1000 nm or less, 300 nm or more and 600 nm or less, 520 nm or more and 2000 nm or less, 520 nm or more and 1500 nm or less, 520 nm or more and 1400 nm or less, 520 nm or more and 1150 nm or less, 520 nm or more and 1000 nm or less, and 520 nm or more and 600 nm or less.
[0069] The thickness direction retardation (Rth) of the biaxially stretched plastic film is preferably 2000 nm or more, more preferably 3000 nm or more, and even more preferably 4000 nm or more. The upper limit of Rth is about 10000 nm, preferably 8000 nm or less, more preferably 7000 nm or less. By setting Rth in the above range, it is possible to more easily suppress rainbow unevenness. Preferred ranges of Rth of the biaxially stretched plastic film include 2000 nm or more and 10000 nm or less, 2000 nm or more and 8000 nm or less, 2000 nm or more and 7000 nm or less, 3000 nm or more and 10000 nm or less, 3000 nm or more and 8000 nm or less, 3000 nm or more and 7000 nm or less, 4000 nm or more and 10000 nm or less, 4000 nm or more and 8000 nm or less, and 4000 nm or more and 7000 nm or less. In order to set the Rth of the biaxially stretched plastic film within the above range, it is preferable to increase the stretch ratios in the longitudinal and transverse directions. By increasing the stretch ratios in the longitudinal and transverse directions, the refractive index nz in the thickness direction of the biaxially stretched plastic film decreases, making it easier to increase Rth. In addition, by reducing the nz of the biaxially stretched plastic film, it is easier to reduce the value of "(α+β) / 2". When the value of "(α+β) / 2" is reduced, the value of (α+β) / 2 moves away from the vicinity of the Brewster angle, making it easier to suppress fluctuations in the reflectance of P waves and S waves at angles before and after (α+β) / 2.
[0070] By setting the in-plane retardation and thickness direction retardation within the above ranges, the degree of stretching of the biaxially oriented plastic film can be made closer to uniform biaxiality, and the mechanical strength of the biaxially oriented plastic film can be improved.
[0071] The in-plane retardation (Re) and the thickness retardation (Rth) are expressed by the following formulas (1) and (2) using the refractive index nx in the slow axis direction, which is the direction in which the refractive index is the largest, the refractive index ny in the fast axis direction, which is the direction perpendicular to the slow axis direction, the refractive index nz in the thickness direction of the plastic film, and the thickness T [nm] of the plastic film. In this specification, the in-plane retardation and the thickness retardation mean values at a wavelength of 550 nm. Re = (nx-ny) × T [nm] (1) Rth = ((nx + ny) / 2 - nz) × T [nm] (2)
[0072] The direction of the slow axis, the in-plane retardation, and the retardation in the thickness direction can be measured, for example, by using a product name "RETS-100" manufactured by Otsuka Electronics Co., Ltd. When measuring the in-plane retardation and the like using the product name "RETS-100" manufactured by Otsuka Electronics Co., Ltd., it is preferable to prepare for the measurement according to the following procedures (A1) to (A4).
[0073] (A1) First, turn on the RETS-100 light source and leave it for 60 minutes or more to stabilize it. After that, select the rotating analyzer method and select θ mode (angle direction phase difference measurement and Rth calculation mode). By selecting this θ mode, the stage becomes a tilt rotation stage. (A2) Next, enter the following measurement conditions into the RETS-100. (Measurement conditions) Retardation measurement range: Rotating analyzer method Measurement spot diameter: φ5mm Tilt angle range: 0° Measurement wavelength range: 400nm to 800nm - Average refractive index of plastic film. For example, in the case of PET film, N = 1.617. The average refractive index N of plastic film can be calculated based on nx, ny, and nz using the formula (N = (nx + ny + nz) / 3). Thickness: Thickness measured separately using SEM or optical microscope (A3) Next, background data is obtained without placing a sample in the apparatus, in a closed system, and every time the light source is turned on. (A4) After that, the sample is placed on the stage inside the device and measured.
[0074] The in-plane retardation, thickness direction retardation, and the direction of the slow axis described later are preferably averaged values of five measured points on a sample cut out of a biaxially stretched plastic film, the sample being 50 mm long x 50 mm wide. The five measurement points are one at the center and four points 10 mm away from the four corners toward the center (five points indicated by black circles in FIG. 7).
[0075] The biaxially stretched plastic film preferably has an in-plane retardation relative to the retardation in the thickness direction (in-plane retardation / thickness retardation) of 0.10 or less. In this specification, the in-plane retardation relative to the retardation in the thickness direction may be expressed as "Re / Rth". Re / Rth can be measured, for example, as follows.
[0076] The in-plane retardation values measured at five points on the sample are defined as Re1, Re2, Re3, Re4, and Re5, respectively, and the thickness direction retardation values measured at five points on the sample are defined as Rth1, Rth2, Rth3, Rth4, and Rth5, respectively. In the biaxially stretched plastic film, the average of Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 is preferably 0.10 or less.
[0077] A small ratio (Re / Rth) of the in-plane retardation to the thickness retardation means that the biaxial stretching of the biaxially stretched plastic film approaches uniform biaxiality. Therefore, by making Re / Rth 0.10 or less, the mechanical strength of the biaxially stretched plastic film can be improved. Re / Rth is more preferably 0.07 or less, and even more preferably 0.05 or less. The lower limit of Re / Rth is about 0.01. The Re / Rth of a completely uniaxially stretched plastic film is 2.0. General-purpose uniaxially stretched plastic films are also slightly stretched in the machine direction. For this reason, the Re / Rth of general-purpose uniaxially stretched plastic films is about 1.0.
[0078] Each of Re1 / Rth1, Re2 / Rth2, Re3 / Rth3, Re4 / Rth4 and Re5 / Rth5 is preferably 0.10 or less, more preferably 0.07 or less, and even more preferably 0.05 or less. The lower limit of these ratios is about 0.01.
[0079] The biaxially stretched plastic film preferably satisfies the following condition 2. <Condition 2> The direction of the slow axis is measured at five points on the sample. When the angles formed between any one side of the sample and the direction of the slow axis at each measurement point are defined as D1, D2, D3, D4, and D5, respectively, the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is 5.0 degrees or more.
[0080] When the slow axis of the biaxially stretched plastic film is neatly oriented, rainbow unevenness tends to be easily visible. On the other hand, when the slow axis of the biaxially stretched plastic film is made uneven, the rainbow unevenness becomes blurred and difficult to see. Therefore, by satisfying condition 2, it is possible to easily suppress the rainbow unevenness from being seen by the naked eye. In other words, by satisfying condition 2, it is possible to easily satisfy the condition that the difference between the maximum and minimum values of ΔEab is less than 17.0. General-purpose stretched plastic films are designed so that the direction of the slow axis does not shift. However, as mentioned above, by deliberately shifting the direction of the slow axis of the plastic film, it becomes easier to suppress rainbow unevenness. Also, even if the slow axis varies over a large area, the effect of suppressing rainbow unevenness is small, but by varying the slow axis over a relatively small area of 50 mm length x 50 mm width, it becomes easier to suppress rainbow unevenness.
[0081] In condition 2, any one side of the sample that is the reference for the angle with the slow axis direction may be either a vertical or horizontal side of the sample, so long as the same side is used as the reference for all of D1 to D5.
[0082] Moreover, satisfying condition 2 is preferable in that the biaxially stretched plastic film can have good bending resistance. On the other hand, general-purpose oriented films in which the slow axes are aligned without satisfying condition 2 break after bending tests or have a strong bending tendency. Specifically, a uniaxially stretched film such as that in Patent Document 1 breaks when bent along the slow axis, and has a strong bending tendency when bent in a direction perpendicular to the slow axis. Moreover, a general-purpose biaxially stretched film has a strong bending tendency when bent in a direction perpendicular to the slow axis. A biaxially stretched plastic film that satisfies condition 2 is preferable in that it is possible to prevent the film from retaining a bending habit or breaking after a bending test, regardless of the bending direction.
[0083] The difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is preferably 6.0 degrees or more, more preferably 8.0 degrees or more, and further preferably 10.0 degrees or more. If the difference between the maximum value of D1 to D5 and the minimum value of D1 to D5 is too large, the orientation of the plastic film tends to be low and the mechanical strength tends to decrease. Therefore, the difference is preferably 20.0 degrees or less, more preferably 17.0 degrees or less, and even more preferably 15.0 degrees or less.
[0084] In condition 2, preferred ranges for the difference between the maximum and minimum values of D1 to D5 are, for example, 5.0 degrees or more and 20.0 degrees or less, 6.0 degrees or more and 20.0 degrees or less, 8.0 degrees or more and 20.0 degrees or less, 10.0 degrees or more and 20.0 degrees or less, 5.0 degrees or more and 17.0 degrees or less, 6.0 degrees or more and 17.0 degrees or less, 8.0 degrees or more and 17.0 degrees or less, 10.0 degrees or more and 17.0 degrees or less, 5.0 degrees or more and 15.0 degrees or less, 6.0 degrees or more and 15.0 degrees or less, 8.0 degrees or more and 15.0 degrees or less, and 10.0 degrees or more and 15.0 degrees or less.
[0085] In the biaxially stretched plastic film, D1 to D5 are preferably 5 degrees or more and 30 degrees or less, or 60 degrees or more and 85 degrees or less, more preferably 7 degrees or more and 25 degrees or less, or 65 degrees or more and 83 degrees or less, and even more preferably 10 degrees or more and 23 degrees or less, or 67 degrees or more and 80 degrees or less. By setting D1 to D5 to 5 degrees or more or 85 degrees or less, respectively, it is possible to easily prevent blackout when viewed through polarized sunglasses. Also, by setting D1 to D5 to 30 degrees or less or 60 degrees or more, respectively, it is possible to easily prevent a decrease in mechanical strength due to a decrease in the orientation of the plastic film.
[0086] Biaxially stretched plastic films may be in the form of a sheet or a roll, for example. In either case, a sample measuring 50 mm long by 50 mm wide may be cut from any location on the plastic film, but if the longitudinal and transverse directions of the sheet and roll can be confirmed, the sample shall be cut along the confirmed longitudinal and transverse directions. For example, in the case of a roll, the flow direction (MD direction) of the roll may be regarded as the longitudinal direction, and the width direction (TD direction) of the roll may be regarded as the transverse direction. Also, if the flow direction and transverse direction of the sheet can be confirmed, the flow direction may be regarded as the longitudinal direction, and the transverse direction may be regarded as the transverse direction. If it is difficult to confirm the flow direction and transverse direction of the sheet, and the sheet is a rectangle or a square, the longitudinal and transverse directions may be confirmed on the four sides constituting the rectangle or square. If it is difficult to confirm the flow direction and transverse direction of the sheet, and the sheet is a shape other than a rectangle or a square (circle, triangle, etc.), a rectangle or square with the largest area that does not protrude from the outer frame shape of the sheet may be drawn, and the longitudinal and transverse directions may be confirmed on the sides of the drawn rectangle or square. In addition, when multiple samples of 50 mm length × 50 mm width can be taken from a sheet-like plastic film, the ratio of the samples that satisfy condition 2 among the multiple samples is preferably 50% or more, more preferably 70% or more, even more preferably 90% or more, and even more preferably 100%. The same applies to the in-plane retardation, thickness direction retardation, and Re / Rth.
[0087] It is preferable that the biaxially stretched plastic film does not crack or break after 100,000 times (more preferably after 300,000 times) of the folding test shown in the examples. In addition, when the biaxially stretched plastic film is placed on a horizontal table after 100,000 times (more preferably after 300,000 times), the angle at which the end of the sample rises from the table is preferably 20 degrees or less, more preferably 15 degrees or less. The angle at which the end of the sample rises from the table is 15 degrees or less means that the film is unlikely to develop a crease due to folding. In addition, it is preferable that the biaxially stretched plastic film shows the above-mentioned results (no cracks, breaks, or creases due to folding are not developed. The angle at which the end of the sample rises after the test is 20 degrees or less) in both the average of the slow axis direction and the average of the fast axis direction of the biaxially stretched plastic film. When a uniaxially stretched plastic film is subjected to a folding test, it breaks in the stretching direction, and retains a strong bend in the direction perpendicular to the stretching direction.
[0088] <<Specific configuration of biaxially stretched plastic film>> The laminate structure of the biaxially stretched plastic film may be a single-layer structure or a multi-layer structure, of which the single-layer structure is preferred. In order to suppress rainbow unevenness while improving mechanical strength, it is preferable to reduce the in-plane retardation of the biaxially stretched plastic film. In order to reduce the in-plane retardation of the stretched plastic film, it is important to finely control the stretching, such as making the stretching in the longitudinal direction and the transverse direction close to uniform. Regarding fine control of the stretching, it is difficult to finely control the stretching in the multilayer structure due to differences in the physical properties of each layer, but the single-layer structure is preferable because it is easy to finely control the stretching.
[0089] Examples of resin components constituting the biaxially stretched plastic film include polyester, polyimide, polyethersulfone, polysulfone, polypropylene, polymethylpentene, polyvinyl chloride, polyvinyl acetal, polyether ketone, polymethyl methacrylate, polycarbonate, polyurethane, and amorphous olefin (Cyclo-Olefin-Polymer: COP). Among these, polyester is preferred because it is easy to improve the mechanical strength. That is, the biaxially stretched plastic film is preferably a polyester film, and more preferably a biaxially stretched polyethylene terephthalate film.
[0090] In addition, biaxially oriented plastic films are stretched to improve mechanical strength. x >n y ≧n z It is preferable that the relationship of n x >n y ≧n z In order to satisfy the above relationship, the resin component constituting the biaxially stretched plastic film is preferably a positive birefringent material. n x >n y ≧n z In a biaxially stretched plastic film that satisfies the above relationship, the phase difference in the oblique direction gradually decreases as it inclines along the direction of the slow axis, and becomes 0 nm in the vicinity of "(α+β) / 2". As described above, "color distortion" is easily felt when the oblique phase difference is 0 nm when the elevation angle along the slow axis is "(α+β) / 2". In the present disclosure, x >n y ≧n z Even when a biaxially stretched plastic film that satisfies the above relationship is used, color distortion can be easily suppressed by making the difference between the maximum and minimum values of ΔEab less than 17.0.
[0091] Positively birefringent materials include polyesters, polycarbonates, cycloolefin polymers, polyimide films and polyamides.
[0092] Examples of polyesters constituting the biaxially stretched polyester film include polyethylene terephthalate (PET), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), etc. Among these, PET is preferred because it has low intrinsic birefringence and is easy to reduce the in-plane retardation.
[0093] The biaxially stretched plastic film may contain additives such as ultraviolet absorbers, light stabilizers, antioxidants, antistatic agents, flame retardants, antigelling agents, and surfactants.
[0094] The lower limit of the thickness of the biaxially stretched plastic film is preferably 10 μm or more, more preferably 15 μm or more, more preferably 20 μm or more, more preferably 25 μm or more, more preferably 30 μm or more, and the upper limit is preferably 200 μm or less, more preferably 180 μm or less, more preferably 150 μm or less, more preferably 100 μm or less, more preferably 80 μm or less, more preferably 60 μm or less, more preferably 50 μm or less. In order to reduce the thickness, the thickness of the biaxially stretched plastic film is preferably 50 μm or less. By making the thickness 10 μm or more, it is possible to easily obtain good mechanical strength, and by making the thickness 200 μm or less, it is possible to easily obtain an in-plane retardation of 2500 nm or less.
[0095] Preferred ranges of the thickness of the biaxially stretched plastic film are, for example, 10 μm or more and 200 μm or less, 15 μm or more and 200 μm or less, 20 μm or more and 200 μm or less, 25 μm or more and 200 μm or less, 30 μm or more and 200 μm or less, 10 μm or more and 180 μm or less, 15 μm or more and 180 μm or less, 20 μm or more and 180 μm or less, 25 μm or more and 180 μm or less, 30 μm or more and 180 μm or less, 10 μm or more and 150 μm or less, 15 μm or more and 150 μm or less, 20 μm or more and 150 μm or less, 25 μm or more and 150 μm or less, 30 μm or more and 150 μm or less, 10 μm or more and 100 μm or less, 15 μm or more and 100 μm or less, 20 μm or more and 100 μm or less, 25 μm or more and 100 μm or less, 30 μm or more and 100 μm or less, 10 μm or more and 80 μm or less, 15 μm or more and 80 μm or less, 20 μm or more and 80 μm or less, 25 μm or more and 80 μm or less, 30 μm or more and 80 μm or less, 10 μm or more and 60 μm or less, 15 μm or more and 60 μm or less, 20 μm or more and 60 μm or less, 25 μm or more and 60 μm or less, 30 μm or more and 60 μm or less, 10 μm or more and 50 μm or less, 15 μm or more and 50 μm or less, 20 μm or more and 50 μm or less, 25 μm or more and 50 μm or less, 30 μm or more and 50 μm or less.
[0096] The biaxially stretched plastic film preferably has a haze according to JIS K7136:2000 of 3.0% or less, more preferably 2.0% or less, even more preferably 1.5% or less, and even more preferably 1.0% or less. Furthermore, the biaxially stretched plastic film preferably has a total light transmittance according to JIS K7361-1:1997 of 80% or more, more preferably 85% or more, and even more preferably 90% or more.
[0097] A biaxially stretched plastic film can be obtained by stretching a resin layer containing the components that constitute the plastic film. The stretching method includes sequential biaxial stretching and simultaneous biaxial stretching.
[0098] -Sequential biaxial stretching- In sequential biaxial stretching, the casting film is stretched in the machine direction, and then stretched in the width direction of the film. The stretching in the machine direction is usually performed by the difference in peripheral speed between a pair of stretching rolls. The stretching in the machine direction may be performed in one stage, or may be performed in multiple stages using a plurality of pairs of stretching rolls. In order to suppress excessive variation in optical properties such as in-plane retardation, it is preferable to place a plurality of nip rolls close to the stretching roll. The stretching ratio in the machine direction is usually 2 to 15 times, and in order to suppress excessive variation in optical properties such as in-plane retardation, it is preferably 2 to 7 times, more preferably 3 to 5 times, and even more preferably 3 to 4 times. In order to suppress excessive variation in optical properties such as in-plane retardation, the stretching temperature is preferably from the glass transition temperature of the resin to the glass transition temperature + 100° C. In the case of PET, the temperature is preferably from 70° C. to 120° C., more preferably from 80° C. to 110° C., and even more preferably from 95° C. to 110° C. Regarding the stretching temperature, the average in-plane retardation tends to be small by shortening the stretching section at low temperature by heating the film quickly, whereas the average in-plane retardation tends to be large and the variation of the slow axis tends to be small by lengthening the stretching section at low temperature by heating the film slowly. In addition, when heating during stretching, it is preferable to use a heater that generates turbulent flow. By heating with wind containing turbulent flow, temperature differences occur in fine regions within the film plane, and the temperature differences cause fine deviations in the orientation axis, making it easier to satisfy condition 2. In addition, by having the plastic film satisfy condition 2, it is easier to make the difference between the maximum and minimum values of ΔEab less than 17.0.
[0099] The film stretched in the machine direction may be provided with functions such as easy slippage, easy adhesion, antistatic properties, etc., by in-line coating. Furthermore, before in-line coating, surface treatment such as corona treatment, flame treatment, plasma treatment, etc. may be performed as necessary. The coating film formed by in-line coating in this way is very thin, with a thickness of about 10 nm to 2000 nm (and the coating film is stretched even thinner by stretching treatment). In this specification, such a thin layer is not counted as the number of layers constituting the plastic film.
[0100] The stretching in the width direction is usually performed by conveying the film while holding both ends with clips using a tenter method, and stretching the film in the width direction. The stretching ratio in the width direction is usually 2 to 15 times, and in order to suppress excessive variation in optical properties such as in-plane retardation, it is preferably 2 to 5 times, more preferably 3 to 5 times, and even more preferably 3 to 4.5 times. In addition, it is preferable to make the width stretching ratio higher than the longitudinal stretching ratio. The stretching temperature is preferably from the glass transition temperature of the resin to the glass transition temperature + 120°C, and the temperature preferably increases from the upstream to the downstream. Specifically, when the transverse stretching section is divided into two, the difference between the upstream and downstream temperatures is preferably 20°C or more, more preferably 30°C or more, even more preferably 35°C or more, and even more preferably 40°C or more. In the case of PET, the first-stage stretching temperature is preferably 80°C to 120°C, more preferably 90°C to 110°C, and even more preferably 95°C to 105°C.
[0101] The plastic film sequentially biaxially stretched as described above is preferably heat-treated in a tenter at a temperature equal to or higher than the stretching temperature and lower than the melting point in order to impart flatness and dimensional stability. Specifically, in the case of PET, heat setting is preferably performed in the range of 150°C to 255°C, more preferably 200°C to 250°C. In addition, in order to suppress excessive variation in optical properties such as in-plane retardation, it is preferable to perform additional stretching of 1% to 10% in the first half of the heat treatment. After the plastic film is heat-treated, it is slowly cooled to room temperature and then wound up. If necessary, a relaxation treatment or the like may be used in combination with the heat treatment and the slow cooling. The relaxation rate during the heat treatment is preferably 0.5% to 5%, more preferably 0.5% to 3%, even more preferably 0.8% to 2.5%, and even more preferably 1% to 2% in order to suppress excessive variation in optical properties such as in-plane retardation. The relaxation rate during the slow cooling is preferably 0.5% to 3%, more preferably 0.5% to 2%, even more preferably 0.5% to 1.5%, and even more preferably 0.5% to 1.0% in order to suppress excessive variation in optical properties such as in-plane retardation. In order to obtain good flatness, the temperature during slow cooling is preferably 80° C. or higher and 150° C. or lower, more preferably 90° C. or higher and 130° C. or lower, even more preferably 100° C. or higher and 130° C. or lower, and even more preferably 100° C. or higher and 120° C. or lower.
[0102] -Simultaneous biaxial stretching- In the simultaneous biaxial stretching, the casting film is introduced into a simultaneous biaxial tenter, and the film is conveyed while both ends are held by clips, and stretched simultaneously and / or stepwise in the machine direction and width direction. The simultaneous biaxial stretching machine may be of the pantograph type, screw type, drive motor type, or linear motor type, but the drive motor type or linear motor type is preferred because it can change the stretch ratio at any time and can perform relaxation treatment at any location.
[0103] The area ratio of the simultaneous biaxial stretching is usually 6 to 50 times. In order to suppress excessive variation in optical properties such as in-plane retardation, the area ratio is preferably 8 to 30 times, more preferably 9 to 25 times, even more preferably 9 to 20 times, and still more preferably 10 to 15 times. In the simultaneous biaxial stretching, the stretch ratio in the machine direction and the stretch ratio in the width direction are preferably adjusted to the above area ratio within the range of 2 to 15 times. In the case of simultaneous biaxial stretching, in order to suppress in-plane orientation differences, it is preferable that the stretching ratios in the machine direction and the width direction are approximately the same, and that the stretching speeds in the machine direction and the width direction are also approximately the same.
[0104] In order to suppress excessive variation in optical properties such as in-plane retardation, the stretching temperature in the simultaneous biaxial stretching is preferably from the glass transition temperature of the resin to the glass transition temperature + 120° C. In the case of PET, the stretching temperature is preferably from 80° C. to 160° C., more preferably from 90° C. to 150° C., and even more preferably from 100° C. to 140° C.
[0105] The simultaneously biaxially stretched film is preferably subsequently subjected to a heat treatment at a temperature equal to or higher than the stretching temperature and lower than the melting point in a heat fixing chamber in a tenter in order to impart flatness and dimensional stability. The heat treatment conditions are the same as those after the successive biaxial stretching.
[0106] <Low refractive index layer> The low refractive index layer has the role of enhancing the anti-reflection properties of the optical film and of making it easier to suppress rainbow irregularities when viewed with the naked eye. The light traveling from the inside of the image display device toward the viewer is linearly polarized light when it passes through the polarizer, but after passing through the biaxially stretched plastic film, the polarization state of the linearly polarized light is disturbed, and the light becomes a mixture of P waves and S waves. Since there is a difference between the reflectance of P waves and the reflectance of S waves, and the reflectance difference is wavelength dependent, it is considered that rainbow unevenness is visible to the naked eye. Here, when a low refractive index layer is provided on the biaxially stretched plastic film, the reflectance difference can be reduced, and therefore it is considered that rainbow unevenness can be easily suppressed. However, it is difficult to set the difference between the maximum and minimum values of ΔEab within the above range by simply forming a low refractive index layer on a general-purpose biaxially stretched plastic film, and rainbow unevenness cannot be suppressed at a high level. In order to easily set the difference between the maximum and minimum values of ΔEab within the above range, it is preferable to provide variation in the direction of the slow axis of the biaxially stretched plastic film, as described above. The low refractive index layer is preferably formed on the side of the optical film farthest from the biaxially stretched plastic film. By forming a high refractive index layer (described later) adjacent to the low refractive index layer on the biaxially stretched plastic film side of the low refractive index layer, the antireflection properties can be further improved and rainbow unevenness can be more easily suppressed.
[0107] The refractive index of the low refractive index layer is preferably from 1.10 to 1.48, more preferably from 1.20 to 1.45, more preferably from 1.26 to 1.40, more preferably from 1.28 to 1.38, and more preferably from 1.30 to 1.32. The thickness of the low refractive index layer is preferably 80 nm to 120 nm, more preferably 85 nm to 110 nm, and even more preferably 90 nm to 105 nm. The thickness of the low refractive index layer is preferably larger than the average particle size of the low refractive index particles such as hollow particles.
[0108] The method of forming a low refractive index layer can be roughly divided into a wet method and a dry method. The wet method includes a method of forming by a sol-gel method using metal alkoxide or the like, a method of forming by coating a resin with a low refractive index such as a fluororesin, and a method of forming by coating a coating liquid for forming a low refractive index layer in which low refractive index particles are contained in a resin composition. The dry method includes a method of selecting particles having a desired refractive index from the low refractive index particles described later and forming by a physical vapor deposition method or a chemical vapor deposition method. The wet method is superior to the dry method in terms of production efficiency, suppression of oblique reflection hue, and chemical resistance. Among the wet methods, it is preferable to form the low refractive index layer using a coating liquid for forming the low refractive index layer in which low refractive index particles are contained in a binder resin composition in order to improve adhesion, water resistance, scratch resistance, and reduce the refractive index.
[0109] The low refractive index layer is usually located on the outermost surface of the optical film, and therefore is required to have good scratch resistance, and general-purpose low refractive index layers are also designed to have a certain scratch resistance. In recent years, hollow particles with large particle diameters have been used as low-refractive index particles to reduce the refractive index of the low-refractive index layer. The present inventors have found a problem that even if the surface of a low-refractive index layer containing hollow particles with large particle diameters is rubbed with an object with only fine solid matter (e.g., sand) or only oil, and no scratches are visible, the surface is scratched when rubbed with an object with both solid matter and oil (hereinafter, this problem may be referred to as "oil dust resistance"). The action of rubbing with an object with solid matter and oil corresponds to, for example, the action of a user operating a touch panel type image display device with a finger with oil contained in cosmetics and food, etc., and sand contained in the air. Improving the oil dust resistance of the low refractive index layer is preferable because it leads to maintaining the effect of suppressing iridescent unevenness for a long period of time.
[0110] As a result of the study by the present inventors, it was found that the above-mentioned scratches are mainly caused by a part of the hollow particles contained in the low refractive index layer being chipped or the hollow particles falling off. It was thought that the cause of this was the large unevenness caused by the hollow particles formed on the surface of the low refractive index layer. That is, when the surface of the low refractive index layer is rubbed with a finger having solid matter and oil on it, the oil becomes a binder and the finger moves on the surface of the low refractive index layer with the solid matter still attached to the finger. At this time, the phenomenon that a part of the solid matter (for example, a sharp point of sand) enters the recessed part of the low refractive index layer surface, and the phenomenon that the solid matter that entered the recessed part passes through the recessed part together with the finger and overcomes the protruding part (hollow particle) is likely to occur, and at that time, a large force is applied to the protruding part (hollow particle), so it was thought that the hollow particle is damaged or falls off. In addition, it was thought that the resin itself located in the recessed part is also scratched by friction caused by the solid matter, and the hollow particle becomes more likely to fall off due to the damage of the resin. The present inventors have conducted extensive research and found that in order to impart oil dust resistance, it is effective to use hollow particles and non-hollow particles together as low refractive index particles and to uniformly disperse the hollow particles and non-hollow particles. Fig. 8 shows a low refractive index layer in which hollow particles and non-hollow particles are uniformly dispersed, and Fig. 9 shows a cross-sectional photograph of a low refractive index layer in which hollow particles and non-hollow particles are not uniformly dispersed. The cross-sectional photographs of Figs. 8 and 9 were obtained by observation using an electron microscope "Model No.: H-7650" manufactured by Hitachi High-Tech Corporation under the conditions of an emission current of 10 μA, an acceleration voltage of 100 keV, and a filament voltage of 20 V.
[0111] In order to obtain good oil dust resistance, the low refractive index particles preferably include hollow particles and non-hollow particles. The material of the hollow particles and non-hollow particles may be either an inorganic compound such as silica or magnesium fluoride, or an organic compound, but silica is preferred for its low refractive index and strength. The following description will be centered on hollow silica particles and non-hollow silica particles.
[0112] Hollow silica particles refer to particles that have an outer shell layer made of silica, the inside of the particle surrounded by the outer shell layer is hollow, and the inside of the cavity contains air. Hollow silica particles are particles that contain air, and the refractive index is reduced in proportion to the occupancy rate of gas compared to the refractive index of silica itself. Non-hollow silica particles are particles that are not hollow like hollow silica particles. Non-hollow silica particles are, for example, solid silica particles. The shape of the hollow silica particles and non-hollow silica particles is not particularly limited, and may be a perfect sphere, a spheroid, or a nearly spherical shape such as a polyhedron that can approximate a sphere, etc. Among these, in consideration of scratch resistance, a perfect sphere, a spheroid, or a nearly spherical shape is preferable.
[0113] Since hollow silica particles contain air inside, they play a role in lowering the refractive index of the entire low refractive index layer. By using hollow silica particles with a large particle size and a high ratio of air, the refractive index of the low refractive index layer can be further lowered. On the other hand, hollow silica particles tend to have poor mechanical strength. In particular, when hollow silica particles with a large particle size and a high ratio of air are used, the scratch resistance of the low refractive index layer tends to be easily reduced. The non-hollow silica particles, when dispersed in the binder resin, play a role in improving the scratch resistance of the low refractive index layer.
[0114] In order to make hollow silica particles and non-hollow silica particles contained in binder resin at high concentration and to disperse the particles uniformly in the thickness direction in the resin, it is preferable to set the average particle size of hollow silica particles and the average particle size of non-hollow silica particles so that the hollow silica particles are close to each other and the non-hollow particles can be inserted between the hollow silica particles.Specifically, the ratio of the average particle size of non-hollow silica particles to the average particle size of hollow silica particles (average particle size of non-hollow silica particles / average particle size of hollow silica particles) is preferably 0.29 or less, more preferably 0.27 or less.In addition, the ratio of the average particle sizes is preferably 0.05 or more, more preferably 0.10 or more. Considering optical properties and mechanical strength, the average particle size of hollow silica particles is preferably 20nm or more and 100nm or less.Because it is easy to lower the refractive index of the whole low refractive index layer, the average particle size of hollow silica particles is more preferably 50nm or more and 100nm or less, and even more preferably 60nm or more and 80nm or less.In addition, considering dispersibility while preventing aggregation of non-hollow silica particles, the average particle size of non-hollow silica particles is preferably 5nm or more and 20nm or less, and more preferably 10nm or more and 15nm or less.
[0115] The surfaces of the hollow silica particles and non-hollow silica particles are preferably coated with a silane coupling agent, and it is more preferable to use a silane coupling agent having a (meth)acryloyl group or an epoxy group. By subjecting the silica particles to a surface treatment with a silane coupling agent, the affinity between the silica particles and the binder resin is improved, and the silica particles are less likely to aggregate, which makes it easier for the silica particles to be dispersed uniformly.
[0116] Examples of silane coupling agents include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-di methyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, tris-(trimethoxysilylpropyl)isocyanurate, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, phenyltrimethoxysilane, methyltriethoxysilane, dimethyldiethoxysilane, phenyltriethoxysilane, n-propyltrimethoxysilane, n-propyltriethoxysilane, hexyltrimethoxysilane, hexyltriethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, 1,6-bis(trimethoxysilyl)hexane, trifluoropropyltrimethoxysilane, vinyltrimethoxysilane and vinyltriethoxysilane. In particular, it is preferable to use one or more selected from 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane.
[0117] The higher the content of hollow silica particles, the higher the filling rate of hollow silica particles in the binder resin, and the lower the refractive index of the low refractive index layer. Therefore, the content of hollow silica particles is preferably 100 parts by mass or more, more preferably 125 parts by mass or more, relative to 100 parts by mass of the binder resin. On the other hand, if the content of hollow silica particles relative to the binder resin is too high, the hollow silica particles exposed from the binder resin increase, and the binder resin that bonds between particles decreases. Therefore, the hollow silica particles tend to be easily damaged or fall off, and the mechanical strength of the low refractive index layer, such as scratch resistance, tends to decrease. Therefore, the content of hollow silica particles is preferably 400 parts by mass or less, more preferably 300 parts by mass or less, and even more preferably 200 parts by mass or less, relative to 100 parts by mass of the binder resin.
[0118] When the content of non-hollow silica particles is small, even if non-hollow silica particles are present on the surface of the low refractive index layer, it may not affect the hardness increase.In addition, when non-hollow silica particles are contained in a large amount, the effect of shrinkage unevenness caused by polymerization of binder resin can be reduced, and the unevenness generated on the surface of the low refractive index layer after resin hardening can be reduced.Therefore, the content of non-hollow silica particles is preferably 20 parts by mass or more, more preferably 40 parts by mass or more, even more preferably 90 parts by mass or more, and even more preferably 100 parts by mass or more, relative to 100 parts by mass of binder resin. On the other hand, if the content of non-hollow silica particles is too high, the non-hollow silica is easily aggregated, the binder resin shrinks unevenly, and the surface becomes large.Therefore, the content of non-hollow silica particles is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and even more preferably 120 parts by mass or less, relative to 100 parts by mass of binder resin.
[0119] By incorporating hollow silica particles and non-hollow silica particles in the binder resin in the above ratio, the barrier properties of the low refractive index layer can be improved, which is presumably because the silica particles are uniformly dispersed at a high filling rate, thereby inhibiting the permeation of gases and the like. In addition, various cosmetics such as sunscreens and hand creams may contain low-volatility low-molecular-weight polymers. By improving the barrier properties of the low-refractive index layer, it is possible to prevent the low-molecular-weight polymer from penetrating into the coating film of the low-refractive index layer, and to prevent problems (e.g., abnormal appearance) caused by the low-molecular-weight polymer remaining in the coating film for a long period of time.
[0120] The binder resin of the low refractive index layer preferably contains a cured product of an ionizing radiation curable resin composition. The ionizing radiation curable compound contained in the ionizing radiation curable resin composition is preferably a compound having an ethylenically unsaturated bond group. Among them, a (meth)acrylate-based compound having a (meth)acryloyl group is more preferable. Hereinafter, a (meth)acrylate compound having four or more ethylenically unsaturated bond groups will be referred to as a "polyfunctional (meth)acrylate compound." Also, a (meth)acrylate compound having two or more and three or less ethylenically unsaturated bond groups will be referred to as a "low-functional (meth)acrylate compound."
[0121] As the (meth)acrylate-based compound, either a monomer or an oligomer can be used. In particular, in order to suppress uneven shrinkage during curing and to easily smooth the uneven shape of the low refractive index layer surface, it is more preferable that the ionizing radiation curable compound contains a low-functional (meth)acrylate-based compound. The proportion of the low-functional (meth)acrylate compound in the ionizing radiation curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and most preferably 100% by mass. In addition, in order to suppress the uneven shrinkage during curing described above and to facilitate smoothing of the uneven shape of the surface of the low refractive index layer, the low-functional (meth)acrylate compound is preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.
[0122] Among the (meth)acrylate compounds, examples of bifunctional (meth)acrylate compounds include isocyanuric acid di(meth)acrylate, polyalkylene glycol di(meth)acrylates such as ethylene glycol di(meth)acrylate, polyethylene glycol diacrylate, and polybutylene glycol di(meth)acrylate, bisphenol A tetraethoxydiacrylate, bisphenol A tetrapropoxydiacrylate, and 1,6-hexanediol diacrylate. Examples of trifunctional (meth)acrylate compounds include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and isocyanuric acid modified tri(meth)acrylate. Examples of polyfunctional (meth)acrylate compounds having 4 or more functional groups include pentaerythritol tetra(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and dipentaerythritol tetra(meth)acrylate. These (meth)acrylate compounds may be modified as described below.
[0123] Examples of the (meth)acrylate oligomer include acrylate polymers such as urethane (meth)acrylate, epoxy (meth)acrylate, polyester (meth)acrylate, and polyether (meth)acrylate. The urethane (meth)acrylate can be obtained, for example, by reacting a polyhydric alcohol and an organic diisocyanate with a hydroxy (meth)acrylate. In addition, preferred epoxy (meth)acrylates are (meth)acrylates obtained by reacting a tri- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with (meth)acrylic acid, (meth)acrylates obtained by reacting a di- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with a polybasic acid and (meth)acrylic acid, and (meth)acrylates obtained by reacting a di- or higher functional aromatic epoxy resin, alicyclic epoxy resin, aliphatic epoxy resin, or the like with a phenol and (meth)acrylic acid.
[0124] In addition, the (meth)acrylate-based compound may have a part of its molecular skeleton modified in order to suppress uneven shrinkage caused by crosslinking and improve surface smoothness. For example, the (meth)acrylate-based compound may be modified with ethylene oxide, propylene oxide, caprolactone, isocyanuric acid, alkyl, cyclic alkyl, aromatic, bisphenol, or the like. In particular, in order to increase affinity with low refractive index particles (silica particles therein) and suppress aggregation of low refractive index particles, the (meth)acrylate-based compound is preferably modified with alkylene oxide such as ethylene oxide or propylene oxide. The proportion of the alkylene oxide-modified (meth)acrylate compound in the ionizing radiation curable compound is preferably 60% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, even more preferably 95% by mass or more, and most preferably 100% by mass. The alkylene oxide-modified (meth)acrylate compound is preferably a low-functional (meth)acrylate compound, and more preferably a (meth)acrylate compound having two ethylenically unsaturated bond groups.
[0125] Examples of the (meth)acrylate-based compound having two ethylenically unsaturated bond groups modified with alkylene oxide include bisphenol F alkylene oxide modified di(meth)acrylate, bisphenol A alkylene oxide modified di(meth)acrylate, isocyanuric acid alkylene oxide modified di(meth)acrylate, and polyalkylene glycol di(meth)acrylate, among which polyalkylene glycol di(meth)acrylate is preferred. The average repeat unit of the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably 3 or more and 5 or less. In addition, the alkylene glycol contained in the polyalkylene glycol di(meth)acrylate is preferably ethylene glycol and / or polyethylene glycol. Examples of the (meth)acrylate compound having three ethylenically unsaturated bond groups modified with an alkylene oxide include trimethylolpropane alkylene oxide modified tri(meth)acrylate and isocyanuric acid alkylene oxide modified tri(meth)acrylate. The above ionizing radiation curable resins may be used alone or in combination of two or more.
[0126] The low refractive index layer preferably contains a leveling agent for antifouling properties and surface smoothness. The leveling agent may be fluorine-based or silicone-based, but silicone-based is preferred. By including a silicone-based leveling agent, the surface of the low reflectance layer can be made smoother. Furthermore, the slipperiness and antifouling properties (fingerprint wiping ability, large contact angle with pure water and hexadecane) of the surface of the low reflectance layer can be improved.
[0127] The content of the leveling agent is preferably 1 part by mass or more and 25 parts by mass or less, more preferably 2 parts by mass or more and 20 parts by mass or less, and even more preferably 5 parts by mass or more and 18 parts by mass or less, relative to 100 parts by mass of the binder resin. By making the content of the leveling agent 1 part by mass or more, it is possible to easily impart various properties such as antifouling properties. In addition, by making the content of the leveling agent 25 parts by mass or less, it is possible to suppress the deterioration of scratch resistance.
[0128] The low refractive index layer has a maximum height roughness Rz of preferably 110 nm or less, more preferably 90 nm or less, even more preferably 70 nm or less, and even more preferably 60 nm or less. In addition, Rz / Ra (Ra is arithmetic mean roughness) is preferably 12.0 or less, more preferably 10.0 or less. Setting Rz / Ra in the above range is particularly effective when Rz is large, about 90 nm or more and 110 nm or less. In this specification, Ra and Rz are the three-dimensional extension of the two-dimensional roughness parameters described in the Shimadzu Corporation Scanning Probe Microscope SPM-9600 Upgrade Kit Instruction Manual (SPM-9600 February 2016, pp. 194-195). Ra and Rz are defined as follows:
[0129] (Arithmetic mean roughness Ra) When only a reference length (L) is cut out from the roughness curve in the direction of the average line, the X-axis is taken in the direction of the average line of this cut-out portion and the Y-axis is taken in the direction of the longitudinal magnification, and the roughness curve is expressed as y = f(x), the following formula can be used.
[0130]
number
[0131] (Maximum height roughness Rz) A reference length is cut out from the roughness curve in the direction of the average line, and the distance between the peak line and the valley line of this cut out portion is measured in the longitudinal direction of the roughness curve.
[0132] When using a scanning probe microscope SPM-9600 manufactured by SHIMADZU CORPORATION, it is preferable to measure and analyze Ra and Rz under the following conditions, for example. <Measurement conditions> Measurement mode: Phase Scanning range: 5μm×5μm Scanning speed: 0.8Hz to 1Hz Number of pixels: 512 x 512 Cantilever used: NanoWorld Holding AG, product number "NCHR", resonance frequency: 320 kHz, spring constant: 42 N / m <Analysis conditions> Deskew: Line Fit
[0133] Small Rz means that the convex part caused by hollow silica particles in the micro domain is small. Small Rz / Ra means that the irregularities caused by silica particles in the micro domain are uniform, and do not have protruding irregularities with respect to the average elevation difference of the irregularities. In this disclosure, the value of Ra is not particularly limited, but Ra is preferably 15 nm or less, more preferably 12 nm or less, even more preferably 10 nm or less, and even more preferably 6.5 nm or less. By uniformly dispersing the low refractive index particles in the low refractive index layer and by suppressing uneven shrinkage of the low refractive index layer, it becomes easier to satisfy the above ranges of Rz and Rz / Ra.
[0134] By having the Rz and Rz / Ra of the low refractive index layer surface within the above range, the resistance when a solid object overcomes the convex portion (caused by hollow silica particles present near the surface) of the low refractive index layer surface can be reduced. Therefore, even if the solid object is rubbed with oily sand under a load, it is considered that the solid object moves smoothly on the low refractive index layer surface. It is also considered that the hardness of the concave portion itself is increased. As a result, it can be presumed that the breakage or falling off of the hollow silica particles is prevented, and the damage to the binder resin itself is also prevented.
[0135] Surface roughness such as Rz and Ra means the average value of measurements taken at 14 points excluding the minimum and maximum values of measurements taken at 16 points, unless otherwise specified. In this specification, the 16 measurement points are preferably determined by dividing the area inside the 0.5 cm margin from the outer edge of the measurement sample into 5 equal parts vertically and horizontally, and the measurement centers are preferably set at 16 intersections. The measurement sample is preferably 5 cm x 5 cm.
[0136] The low refractive index layer can be formed by applying and drying a coating liquid for forming a low refractive index layer, in which each component constituting the low refractive index layer is dissolved or dispersed. Usually, a solvent is used in the coating liquid for forming a low refractive index layer to adjust the viscosity or to make each component soluble or dispersible. Examples of the solvent include ketones (acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, etc.), ethers (dioxane, tetrahydrofuran, etc.), aliphatic hydrocarbons (hexane, etc.), alicyclic hydrocarbons (cyclohexane, etc.), aromatic hydrocarbons (toluene, xylene, etc.), halogenated carbons (dichloromethane, dichloroethane, etc.), esters (methyl acetate, ethyl acetate, butyl acetate, etc.), alcohols (butanol, cyclohexanol, etc.), cellosolves (methyl cellosolve, ethyl cellosolve, etc.), cellosolve acetates, sulfoxides (dimethyl sulfoxide, etc.), glycol ethers (1-methoxy-2-propyl acetate, etc.), amides (dimethylformamide, dimethylacetamide, etc.), and mixtures of these may also be used.
[0137] If the solvent evaporates too quickly, the solvent will convect violently when the coating liquid for forming a low refractive index layer is dried. Therefore, even if the silica particles in the coating liquid are in a uniformly dispersed state, the state of uniform dispersion is likely to be destroyed by the violent convection of the solvent during drying. For this reason, it is preferable that the solvent contains one with a slow evaporation rate. Specifically, it is preferable to contain a solvent with a relative evaporation rate (relative evaporation rate when the evaporation rate of n-butyl acetate is set to 100) of 70 or less, and more preferably a solvent with a relative evaporation rate of 30 to 60. In addition, the solvent with a relative evaporation rate of 70 or less is preferably 10% by mass to 50% by mass, and more preferably 20% by mass to 40% by mass of the total solvent. Examples of relative evaporation rates for slow evaporating solvents are isobutyl alcohol 64, 1-butanol 47, 1-methoxy-2-propyl acetate 44, ethyl cellosolve 38, and cyclohexanone 32. The remaining solvent (solvent other than the solvent having a slow evaporation rate) is preferably one having excellent resin solubility. The remaining solvent is preferably one having a relative evaporation rate of 100 or more.
[0138] In order to suppress the convection of the solvent during drying and to improve the dispersibility of the silica particles, it is preferable that the drying temperature during the formation of the low refractive index layer is as low as possible. The drying temperature can be appropriately set in consideration of the type of solvent, the dispersibility of the silica particles, the production speed, etc.
[0139] <Reflectance> The optical film of the present disclosure has a reflectance measured from the low refractive index layer side of 2.00% or less, preferably 1.70% or less, more preferably 1.20% or less, and even more preferably 1.00% or less.
[0140] In this specification, the reflectance refers to the luminous reflectance Y value of the CIE 1931 standard color system. The reflectance is preferably calculated as the average value of any 10 points. In this specification, the reflectance of the optical film is measured by preparing a sample by attaching a black plate to the opposite side of the optical film from the side to be measured for reflectance via a transparent adhesive layer, and illuminating the sample with light at an incident angle of 5° from the low refractive index layer side. The light source used for measuring the reflectance is preferably a C light source. The refractive index difference between the transparent adhesive layer and the member (e.g., biaxially stretched plastic film) in contact with the sample is preferably within 0.15, more preferably within 0.10, more preferably within 0.05, and more preferably within 0.01. The black plate preferably has a total light transmittance of 1% or less according to JIS K7361-1:1997, more preferably 0%. The refractive index difference between the resin constituting the black plate and the transparent adhesive layer is preferably within 0.15, more preferably within 0.10, more preferably within 0.05, and more preferably within 0.01.
[0141] <Haze, total light transmittance> The optical film has a haze according to JIS K7136:2000 of preferably 5% or less, more preferably 4% or less, and even more preferably 3% or less. The optical film has a haze according to JIS K7136:2000 of preferably 0.5% or more, more preferably 1.0% or more, and even more preferably 1.5% or more. Furthermore, the optical film preferably has a total light transmittance according to JIS K7361-1:1997 of 90% or more, more preferably 91% or more, and even more preferably 92% or more.
[0142] <Other layers> The optical film of the present disclosure may have layers other than the biaxially stretched plastic film and the low refractive index layer. The low refractive index layer and the layers other than the low refractive index layer are preferably optically isotropic. The layer having optical isotropy refers to a layer having an in-plane retardation of less than 20 nm, preferably 10 nm or less, more preferably 5 nm or less. For example, the optical film of the present disclosure preferably has one or more layers selected from a hard coat layer, an antiglare layer, and a high refractive index layer between the biaxially stretched plastic film and the low refractive index layer.
[0143] <High refractive index layer> The high refractive index layer is formed on the biaxially stretched plastic film side of the low refractive index layer as necessary. When a hard coat layer described later is provided, the high refractive index layer is preferably formed between the hard coat layer and the low refractive index layer.
[0144] The high refractive index layer has a refractive index of preferably 1.53 or more and 1.85 or less, more preferably 1.54 or more and 1.80 or less, more preferably 1.55 or more and 1.75 or less, and even more preferably 1.56 or more and 1.70 or less. The thickness of the high refractive index layer is preferably 200 nm or less, more preferably 50 nm or more and 180 nm or less, and even more preferably 70 nm or more and 150 nm or less. When a high refractive index hard coat layer is used, the thickness is preferably similar to that of the hard coat layer.
[0145] The high refractive index layer can be formed from a coating liquid for forming a high refractive index layer, which contains, for example, a binder resin composition and high refractive index particles. Examples of the binder resin composition include the curable resin composition exemplified in the hard coat layer described later.
[0146] Examples of high refractive index particles include antimony pentoxide, zinc oxide, titanium oxide, cerium oxide, tin-doped indium oxide, antimony-doped tin oxide, yttrium oxide, and zirconium oxide. The refractive index of antimony pentoxide is about 1.79, that of zinc oxide is about 1.90, that of titanium oxide is about 2.3 to 2.7, that of cerium oxide is about 1.95, that of tin-doped indium oxide is about 1.95 to 2.00, that of antimony-doped tin oxide is about 1.75 to 1.85, that of yttrium oxide is about 1.87, and that of zirconium oxide is 2.10.
[0147] The average particle size of the high refractive index particles is preferably 2 nm or more, more preferably 5 nm or more, and even more preferably 10 nm or more. In order to suppress whitening and ensure transparency, the average particle size of the high refractive index particles is preferably 200 nm or less, more preferably 100 nm or less, more preferably 80 nm or less, more preferably 60 nm or less, and more preferably 30 nm or less. The smaller the average particle size of the high refractive index particles, the better the transparency, and by making it 60 nm or less, the transparency can be made extremely good.
[0148] The average particle size of the high refractive index particles or the low refractive index particles can be calculated by the following steps (y1) to (y3). (y1) A cross section of the high refractive index layer or the low refractive index layer is imaged by a TEM or STEM. The acceleration voltage of the TEM or STEM is preferably 10 kV to 30 kV, and the magnification is preferably 50,000 to 300,000. (y2) Randomly extract 10 particles from the observed image, and calculate the particle diameter of each particle. The particle diameter is measured as the distance between two parallel lines that is the maximum distance between the two lines when the cross section of the particle is sandwiched between the two lines. If the particles are aggregated, the aggregated particles are considered to be a single particle and are measured. (y3) The same procedure is carried out five times on a separate observation image of the same sample, and the value obtained from the number average of the particle diameters of a total of 50 particles is regarded as the average particle diameter of the high refractive index particles or low refractive index particles.
[0149] <Hard coat layer> The hard coat layer is formed as necessary to improve the scratch resistance of the optical film. The hard coat layer is preferably formed between the biaxially stretched plastic film and the low refractive index layer. When the optical film further has a high refractive index layer, it is preferable to arrange the hard coat layer, the high refractive index layer and the low refractive index layer in this order on the biaxially stretched plastic film.
[0150] In order to improve scratch resistance, the hard coat layer preferably contains a cured product of a curable resin composition such as a thermosetting resin composition or an ionizing radiation curable resin composition, and more preferably contains a cured product of an ionizing radiation curable resin composition.
[0151] The thermosetting resin composition is a composition that contains at least a thermosetting resin, and is a resin composition that is cured by heating. Examples of the thermosetting resin include acrylic resin, urethane resin, phenol resin, urea melamine resin, epoxy resin, unsaturated polyester resin, silicone resin, etc. In the thermosetting resin composition, a curing agent is added to the curable resin as necessary.
[0152] The ionizing radiation curable resin composition is a composition containing a compound having an ionizing radiation curable functional group (hereinafter, also referred to as "ionizing radiation curable compound"). Examples of the ionizing radiation curable functional group include ethylenically unsaturated bond groups such as (meth)acryloyl group, vinyl group, and allyl group, as well as epoxy group and oxetanyl group. As the ionizing radiation curable compound, a compound having an ethylenically unsaturated bond group is preferred, a compound having two or more ethylenically unsaturated bond groups is more preferred, and among them, a (meth)acrylate-based compound having two or more ethylenically unsaturated bond groups is even more preferred. As the (meth)acrylate-based compound having two or more ethylenically unsaturated bond groups, either a monomer or an oligomer can be used. Here, ionizing radiation refers to electromagnetic waves or charged particle beams that have an energy quantum capable of polymerizing or crosslinking molecules. Usually, ultraviolet rays (UV) or electron beams (EB) are used, but other types of radiation, such as electromagnetic waves such as X-rays and gamma rays, and charged particle beams such as alpha rays and ion beams, can also be used. In this specification, (meth)acrylate means acrylate or methacrylate, (meth)acrylic acid means acrylic acid or methacrylic acid, and (meth)acryloyl group means acryloyl group or methacryloyl group.
[0153] The thickness of the hard coat layer is preferably 0.1 μm or more, more preferably 0.5 μm or more, even more preferably 1.0 μm or more, and even more preferably 2.0 μm or more in order to improve scratch resistance. Also, the thickness of the hard coat layer is preferably 100 μm or less, more preferably 50 μm or less, more preferably 30 μm or less, more preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less in order to suppress curling. The thickness of the hard coat layer is preferably 10 μm or less, more preferably 8 μm or less in order to improve bending resistance.
[0154] 《Anti-glare layer》 The antiglare layer can be formed from, for example, a coating liquid for forming an antiglare layer, which contains a binder resin composition and particles. As the binder resin composition, for example, the curable resin composition exemplified in the hard coat layer can be used.
[0155] The particles may be either organic or inorganic. Examples of the organic particles include particles made of polymethyl methacrylate, polyacrylic-styrene copolymer, melamine resin, polycarbonate, polystyrene, polyvinyl chloride, benzoguanamine-melamine-formaldehyde condensate, silicone, fluorine-based resin, polyester resin, etc. Examples of the inorganic particles include particles made of silica, alumina, antimony, zirconia, titania, etc.
[0156] The average particle size of the particles in the antiglare layer cannot be generally determined because it varies depending on the thickness of the antiglare layer, but is preferably from 1.0 μm to 10.0 μm, more preferably from 2.0 μm to 8.0 μm, and even more preferably from 3.0 μm to 6.0 μm.
[0157] The average particle size of the particles in the antiglare layer can be calculated by the following steps (z1) to (z3). (z1) A transmission observation image of the cross section of the antiglare layer is taken using an optical microscope. The magnification is preferably 500 times or more and 2000 times or less. (z2) Randomly extract 10 particles from the observed image, and calculate the particle diameter of each particle. The particle diameter is measured as the distance between two parallel lines that is the maximum distance between the two lines when the cross section of the particle is sandwiched between the two lines. (z3) The same procedure is repeated five times on a separate observation image of the same sample, and the value obtained from the number average of the particle diameters of a total of 50 particles is regarded as the average particle diameter of the particles in the antiglare layer.
[0158] The particle content in the antiglare layer cannot be generalized as it varies depending on the desired level of antiglare properties, but it is preferably 1 part by mass or more and 100 parts by mass or less, more preferably 5 parts by mass or more and 50 parts by mass or less, and even more preferably 10 parts by mass or more and 30 parts by mass or less, per 100 parts by mass of the resin component. The antiglare layer may contain fine particles having an average particle size of less than 500 nm in order to impart antistatic properties, control the refractive index, and adjust the shrinkage of the antiglare layer due to curing of the curable resin composition.
[0159] The thickness of the antiglare layer is preferably 0.5 μm or more, more preferably 1.0 μm or more, and even more preferably 2.0 μm or more. The thickness of the antiglare layer is preferably 50 μm or less, more preferably 30 μm or more, more preferably 20 μm or less, more preferably 15 μm or less, and even more preferably 10 μm or less. In order to improve the bending resistance, the thickness of the antiglare layer is preferably 10 μm or less, and more preferably 8 μm or less.
[0160] <Example of layer structure> The following (1) to (5) are examples of layer configurations of the optical film of the present disclosure. (1) A configuration having a low refractive index layer on a biaxially stretched plastic film. (2) A structure having a hard coat layer and a low refractive index layer in this order on a biaxially stretched plastic film. (3) A configuration having a high refractive index layer and a low refractive index layer in this order on a biaxially stretched plastic film. (4) A structure having an antiglare layer and a low refractive index layer in this order on a biaxially stretched plastic film. (5) A structure having a hard coat layer, a high refractive index layer, and a low refractive index layer in this order on a biaxially stretched plastic film.
[0161] The total thickness of the optical film is preferably 100 μm or less, more preferably 60 μm or less, in order to maintain mechanical properties, suppress excessive variations in optical properties such as in-plane retardation, and effectively suppress blackout. In the optical film, the balance between the thickness of the biaxially stretched plastic film and the thickness of the layer other than the biaxially stretched plastic film is preferably 10:4 to 10:0.5.
[0162] <Shape, size> The optical film may be in the form of a sheet cut to a predetermined size, or in the form of a roll obtained by winding a long sheet into a roll. The size of the sheet is not particularly limited, but the maximum diameter is about 2 inches to 500 inches, and in the present disclosure, 30 inches to 80 inches is preferable. The "maximum diameter" refers to the maximum length when any two points on the optical film are connected. For example, when the optical film is rectangular, the diagonal line of the rectangular area is the maximum diameter. When the optical film is circular, the diameter is the maximum diameter. The width and length of the roll are not particularly limited, but generally, the width is about 500 mm to 3000 mm, and the length is about 100 m to 5000 m. The optical film in the form of a roll can be cut into sheets according to the size of an image display device or the like. When cutting, it is preferable to remove the ends of the roll, which have unstable physical properties. The shape of the sheet is not particularly limited, and may be, for example, a polygon (triangle, square, pentagon, etc.), a circle, or a random, indefinite shape. More specifically, when the optical film is a square, the aspect ratio is not particularly limited as long as it does not cause any problems as a display screen. For example, the aspect ratio may be 1:1, 4:3, 16:10, 16:9, 2:1, etc.
[0163] <Application> The optical film of the present disclosure can be suitably used as an optical film for an image display device. The optical film of the present disclosure can be suitably used as an optical film arranged on the light exit surface side of a display element of an image display device. In this case, it is preferable to have a polarizer between the display element and the optical film of the present disclosure. In addition, when the biaxially stretched plastic film satisfies condition 2, it is possible to suppress the film from retaining a bending habit or breaking after a bending test, regardless of the folding direction. Therefore, when the biaxially stretched plastic film satisfies condition 2, it can be more suitably used as a plastic film for a curved image display device or a foldable image display device.
[0164] [Polarizing plate] The polarizing plate of the present disclosure has a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, and at least one of the first transparent protective plate and the second transparent protective plate is the optical film of the present disclosure described above. In the polarizing plate, the optical film is preferably disposed so that the surface on the biaxially stretched plastic film side faces the polarizer side.
[0165] Fig. 5 is a cross-sectional view showing an embodiment of a polarizing plate 700 of the present disclosure. The polarizing plate 700 of Fig. 5 has a polarizer 300, a first transparent protective plate (500) arranged on one side of the polarizer, and a second transparent protective plate (600) arranged on the other side of the polarizer. The polarizing plate 700 of Fig. 5 uses an optical film 100 as the first transparent protective plate (500). The polarizing plate 700 of Fig. 5 includes the polarizer 300, the first transparent protective plate (500), and the second transparent protective plate (600) laminated together with an adhesive layer 400 interposed therebetween.
[0166] The polarizing plate is used, for example, in combination with a λ / 4 retardation plate to provide anti-reflection properties. In this case, the λ / 4 retardation plate is disposed on the display element of the image display device, and the polarizing plate is disposed closer to the viewer than the λ / 4 retardation plate. In addition, when the polarizing plate is used for a liquid crystal display device, it is used to provide a liquid crystal shutter function. In this case, the liquid crystal display device is arranged in the order of the lower polarizing plate, the liquid crystal display element, and the upper polarizing plate, and the absorption axis of the polarizer of the lower polarizing plate and the absorption axis of the polarizer of the upper polarizing plate are arranged perpendicular to each other. In the configuration of the liquid crystal display device, it is preferable to use the polarizing plate of the present disclosure as the upper polarizing plate.
[0167] <Transparent protection plate> The polarizing plate of the present disclosure uses the optical film of the present disclosure as at least one of the first transparent protective plate and the second transparent protective plate. It is preferable that both the first transparent protective plate and the second transparent protective plate are the optical film of the present disclosure.
[0168] When one of the first transparent protective plate and the second transparent protective plate is the optical film of the present disclosure described above, the other transparent protective plate is not particularly limited, but is preferably an optically isotropic transparent protective plate. In this specification, the optically isotropic transparent protective plate refers to one having an in-plane retardation of less than 20 nm, preferably 10 nm or less, more preferably 5 nm or less. Examples of the optically isotropic transparent protective plate include an acrylic film, a cyclic polyolefin film, and a triacetyl cellulose (TAC) film. The acrylic film and the cyclic polyolefin film are preferable because the film has a moisture permeability similar to that of the biaxially stretched plastic film, which is less likely to be distorted when the polarizing plate absorbs water and can protect the polarizer well. Furthermore, when only one of the first transparent protective plate and the second transparent protective plate is the optical film of the present disclosure described above, it is preferable to use the optical film of the present disclosure described above as the transparent protective plate on the light exit side.
[0169] <Polarizer> Examples of polarizers include sheet-type polarizers (polyvinyl alcohol film, polyvinyl formal film, polyvinyl acetal film, ethylene-vinyl acetate copolymer saponified film, etc.) made by stretching a film dyed with iodine or the like, wire grid-type polarizers made of a large number of metal wires arranged in parallel, coating-type polarizers coated with lyotropic liquid crystal and a dichroic guest-host material, multilayer thin film-type polarizers, etc. These polarizers may be reflective polarizers that have the function of reflecting polarized components that are not transmitted.
[0170] The polarizer is preferably disposed so that the angle between its absorption axis and the slow axis of the biaxially stretched plastic film is within 90 degrees ±5 degrees, more preferably within 90 degrees ±3 degrees, and even more preferably within 90 degrees ±1 degree.
[0171] [Image display device (1)] The image display device (1) of the present disclosure is an image display device having a display element, and a polarizer and an optical film arranged on the light-emitting surface side of the display element, the optical film being the optical film of the present disclosure described above, arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees, and the surface of the optical film on the low refractive index layer side faces the opposite side to the display element. The angle is preferably within 90 degrees ± 3 degrees, more preferably within 90 degrees ± 1 degree.
[0172] FIG. 6 is a cross-sectional view showing an embodiment of an image display device (1) of the present disclosure and an image display device (2) described below. 6 includes an optical film 100 on the light emission surface side (upper side in FIG. 6) of a display element 800. In addition, each image display device 100 in FIG. 6 includes a polarizer 300 between the display element 800 and the optical film 100.
[0173] It should be noted that the image display device 1000 is not limited to the form shown in Fig. 6. For example, while the components constituting the image display device 1000 are arranged at a predetermined interval in Fig. 6, it is preferable that the components are integrated and laminated via an adhesive layer or the like. The image display device may also include components (other optical films, etc.) that are not shown.
[0174] <Display element> Examples of display elements include liquid crystal display elements, EL display elements (organic EL display elements, inorganic EL display elements), plasma display elements, and the like. Furthermore, examples include LED display elements such as mini LEDs and micro LED display elements, and liquid crystal display elements and LED display elements using QDs. When the display element of the display device is a liquid crystal display element, a backlight is required on the surface of the liquid crystal display element opposite to the resin sheet.
[0175] The image display device may be an image display device equipped with a touch panel function. Examples of touch panels include resistive, capacitive, electromagnetic induction, infrared, and ultrasonic touch panels. The touch panel function may be added to a display element, such as an in-cell touch panel liquid crystal display element, or may be a display element having a touch panel placed on it.
[0176] Furthermore, if the biaxially stretched plastic film satisfies condition 2, the optical film can be prevented from retaining a bending habit or from breaking after a bending test. Therefore, if the biaxially stretched plastic film satisfies condition 2, the image display device is preferably a curved image display device or a foldable image display device. When the image display device is a curved image display device or a foldable image display device, the display element is preferably an organic EL display element.
[0177] <Other plastic films> The image display device of the present disclosure may include other plastic films as long as the effects of the present disclosure are not impaired. As the other plastic films, those having optical isotropy are preferred.
[0178] [Image display device (2)] The image display device of the present disclosure is an image display device having a polarizer and an optical film on a light exit surface of a display element, the polarizer is disposed such that an angle between the direction of the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees; the polarizer and the biaxially stretched plastic film of the optical film are disposed so that an angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees; The optical film has a low refractive index layer on a biaxially stretched plastic film having an in-plane retardation of less than 2500 nm, the low refractive index layer being located on the outermost surface of the optical film, and has a region in which the difference between the maximum and minimum values of ΔEab is less than 17.0. Here, measurement 1A is performed on laminate 1A to calculate the L*, a*, and b* values in the L*a*b* color system. Measurement 2A is performed on laminate 2A to calculate the L*, a*, and b* values in the L*a*b* color system. Based on the results of measurements 1A and 2A, ΔEab is calculated under condition 1A.
[0179] <Measurement 1A> A laminate 1A is prepared by laminating a polarizer and the optical film in this order on a display element. In the laminate 1A, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is also arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees. The display element of the laminate 1A is set to white, and the transmitted light emitted from the low refractive index layer side of the laminate 1A is measured at 1 degree intervals at elevation angles of 0 degrees or more and 80 degrees or less and azimuth angles of 0 degrees or more and 359 degrees or less, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows:
[0180] <Measurement 2A> A laminate 2A was prepared by laminating a polarizer on the same display element as in the measurement 1A. The display element of the laminate 2A is set to white, and the transmitted light exiting from the polarizer side of the laminate 2A is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to approximately the same as that of measurement 1A within the plane.
[0181] <Condition 1A> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2A from the L* value of measurement 1A. ΔL* is grayscaled from the maximum value to the minimum value in a specified gradation and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L*, a*, and b* values of Measurement 1A at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2, and the L*, a*, and b* values of Measurement 2A at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2.
[0182] "Laminate 1A" in measurement 1A of the image display device (2) refers to the image display device (2). Also, "laminate 2" in measurement 1B of the image display device (2) refers to the image display device (2) excluding the optical film of the present disclosure described above.
[0183] Measurement 1A and Measurement 2A in the image display device (2) of the present disclosure are the same as Measurement 1 and Measurement 2 in the optical film of the present disclosure described above, except that the surface light source and the display element are different. In addition, the preferred embodiments of Measurement 1A and Measurement 2A are the same as the preferred embodiments of Measurement 1 and Measurement 2 (for example, the preferred ranges of the L* value, a* value, and b* value in the state of laminate 2A are the same as the preferred ranges of the L* value, a* value, and b* value in the state of laminate 2). In addition, the preferred embodiment of Condition 1A is the same as the preferred embodiment of Condition 1 described above.
[0184] [How to select optical films for image display devices] The method for selecting an optical film for an image display device according to the present disclosure is a method for selecting an optical film for an image display device having a polarizer and an optical film on a light exit surface of a display element, the image display device being arranged so that the direction of the absorption axis of the polarizer is parallel to the left-right direction or the up-down direction of the display element, the method including the step of selecting an optical film X that satisfies a judgment condition that the optical film X is an optical film having a low refractive index layer on a biaxially stretched plastic film having an in-plane retardation of less than 2500 nm, the low refractive index layer being located on the outermost surface of the optical film X, and having a region in which the difference between the maximum and minimum values of ΔEab is less than 17.0. Here, measurement 1B is performed on laminate 1B to calculate the L*, a*, and b* values in the L*a*b* color system. Measurement 2B is performed on laminate 2B to calculate the L*, a*, and b* values in the L*a*b* color system. Based on the results of measurements 1B and 2B, ΔEab is calculated under condition 1B.
[0185] <Measurement 1B> A laminate 1B is prepared by laminating a polarizer and the optical film X in this order on a display element. In the laminate 1B, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film X is within 90 degrees ±5 degrees. The display element of the laminate 1B is set to white, and the transmitted light emitted from the low refractive index layer side of the laminate 1B is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows:
[0186] <Measurement 2B> A laminate 2B was prepared by laminating a polarizer on the same display element as in the measurement 1B. The display element of the laminate 2B is set to white, and the transmitted light emerging from the polarizer side of the laminate 2B is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to be approximately the same as that of measurement 1B within the plane.
[0187] <Condition 1B> For all elevation angles and azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2B from the L* value of measurement 1B. ΔL* is grayscaled from the maximum value to the minimum value in a specified gradation and displayed in grayscale on a two-dimensional coordinate system in which the elevation angle is represented by concentric circles and the azimuth angle is represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. Regarding the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L*, a*, and b* values of measurement 1B at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2, and the L*, a*, and b* values of measurement 2B at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α+β) / 2.
[0188] In the method for selecting an optical film for an image display device according to the present disclosure, "an image display device in which the direction of the absorption axis of the polarizer is arranged parallel to the left-right direction or the up-down direction of the display element" means an image display device in which the angle between the direction of the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. The angle is preferably within ±3 degrees, more preferably within ±5 degrees.
[0189] Measurement 1B and Measurement 2B in the method for selecting an optical film for an image display device of the present disclosure are the same as Measurement 1 and Measurement 2 of the optical film of the present disclosure described above, except that the surface light source and the display element are different. In addition, the preferred embodiments of Measurement 1B and Measurement 2B are the same as the preferred embodiments of Measurement 1 and Measurement 2 (for example, the preferred ranges of the L* value, a* value, and b* value in the state of laminate 2B are the same as the preferred ranges of the L* value, a* value, and b* value in the state of laminate 2). In addition, the preferred embodiment of Condition 1B is the same as the preferred embodiment of Condition 1 described above.
[0190] The method for selecting an optical film for an image display device according to the present disclosure preferably further includes an additional judgment condition as a judgment condition, which may include a preferred embodiment of the optical film according to the present disclosure (e.g., retardation in the thickness direction, surface roughness, etc.). The method for selecting an optical film for an image display device according to the present disclosure is useful as a method for selecting an optical film for an image display device having a polarizer on the light-emitting surface side of a display element, and is particularly useful as a method for selecting an optical film for an image display device in which the direction of the absorption axis of the polarizer is arranged parallel to the left-right direction or the up-down direction of the display element. EXAMPLES
[0191] Next, the present disclosure will be described in more detail with reference to examples, but the present disclosure is not limited by these examples in any way.
[0192] 1. Measurement, Evaluation The atmosphere for the following measurements and evaluations shall be at a temperature of 23°C ± 5°C and a relative humidity of 40% RH or more and 65% RH or less. Also, before the measurements and evaluations, the sample shall be exposed to the above atmosphere for 30 minutes or more.
[0193] 1-1. In-plane retardation (Re), retardation in the thickness direction (Rth), and direction of the slow axis Samples measuring 50 mm in length and 50 mm in width were cut out from the plastic films used in the examples, comparative examples, and reference examples prepared or prepared in "2" described below. At that time, the flow direction (MD direction) of the plastic film was regarded as the longitudinal direction, and the width direction (TD direction) of the plastic film was regarded as the transverse direction. For a total of five locations, namely four locations 10 mm from the four corners of the sample towards the center and the center of the sample, the in-plane retardation, retardation in the thickness direction, and direction of the slow axis were measured. The averages of Re1 to Re5 calculated from the measurement results are shown in Table 1. The measuring device used was the product named "RETS-100 (measurement spot: diameter 5 mm)" manufactured by Otsuka Electronics Co., Ltd. The direction of the slow axis was measured in the range of 0 degrees or more and 90 degrees or less with the flow direction (MD direction) of the plastic film as the reference 0 degrees.
[0194] 1-2. Flexural resistance Samples in the form of strips with a short side (TD direction) of 30 mm × a long side (MD direction) of 100 mm were cut out from the plastic films used in the examples, comparative examples, and reference examples prepared or made in the following "2". Both ends of the short side (30 mm) of the sample were fixed to a durability tester (product name "DLDMLH-FS", manufactured by YUASA SYSTEM CO., LTD.) (fixing the area 10 mm from the tip), and a continuous folding test of folding 180 degrees was performed 100,000 times. The folding speed was 120 times per minute. A more detailed method of the folding test is shown below. After the folding test, the strip-shaped sample was placed on a horizontal table, and the angle at which the end of the sample lifted from the table was measured. If the angle is 15 degrees or less, it is the passing level. The results are shown in Table 1. Samples that broke during the process were regarded as "broken". <MD direction> Samples in the form of strips with a short side (MD direction) of 30 mm × a long side (TD direction) of 100 mm were cut out from the plastic films used in the examples, comparative examples, and reference examples prepared or made in the following "2", and the same evaluation as above was performed.
[0195] <Details of the folding test> As shown in FIG. 10(A), in the continuous folding test, first, the side portion 10C of the plastic film 10 and the side portion 10D facing the side portion 10C are respectively fixed by the fixing portions 60 arranged in parallel. The fixing portion 60 is slidable in the horizontal direction. Next, as shown in FIG. 10(B), by moving the fixing portions 60 closer to each other, the plastic film 10 is deformed to be folded. Further, as shown in FIG. 10(C), after moving the fixing portions 60 to a position where the distance between the two opposing side portions fixed by the fixing portions 60 of the plastic film 10 becomes 2 mm, the fixing portions 60 are moved in the reverse direction to eliminate the deformation of the plastic film 10. 10(A) to 10(C), the plastic film 10 can be folded 180 degrees by moving the fixing part 60. Moreover, by performing a continuous folding test so that the bent part 10E of the plastic film 10 does not protrude from the lower end of the fixing part 60 and controlling the distance between the fixing parts 60 at their closest point to 2 mm, the distance between the two opposing sides of the optical film 10 can be set to 2 mm.
[0196] 1-3. Calculating the difference between the maximum and minimum values of ΔEab A liquid crystal display device (EIZO Corporation's product name "EV2450", width: 527.0 mm, height: 596.4 mm, the absorption axis of the polarizer is parallel to the vertical direction of the screen, backlight: a backlight using white light-emitting diodes) was prepared, which had a polarizer on a liquid crystal display element. This liquid crystal display device was regarded as laminate 2. The liquid crystal display device (laminate 2) was set to display white in a darkroom environment, and measurement 2 of this specification was carried out at each angle using ELDIM Corporation's product name "EzContrast". The measurement area was a circle with a diameter of 2 mm (area approximately 3.14 mm 2 It is. Next, laminate 1 was prepared by disposing the optical films of the Examples and Comparative Examples on the liquid crystal display device via an adhesive layer. At this time, the polarizer was disposed so that the absorption axis of the polarizer and the slow axis of the plastic film of the optical film were at 90 degrees. Laminate 1 was then displayed in white in a darkroom environment, and measurement 1 of the present specification was carried out at each angle using ELDIM's product name "EzContrast". The measurement area was a circle with a diameter of 2 mm (area of approximately 3.14 mm2). 2 and was made to match the area of measurement 1. Measurements 1 and 2 were performed at the center positions in the plane of Laminate 1 and Laminate 2. Next, ΔEab at each azimuth angle was calculated based on steps (3-1) to (3-4) in the specification, and the difference between the maximum and minimum values of ΔEab was calculated. Steps (3-1) to (3-4) were performed using ELDIM's product "EzContrast" and its accompanying software "EzCom" (the gradation level in (3-1) above is 16 gradations). The results are shown in Table 1. In the state of Laminate 2, the averages of the L* value, a* value, and b* value, and the variations (3σ) of the L* value, a* value, and b* value were as follows: In other words, in Measurement 2, the averages of the L* value, a* value, and b* value, and the variations (3σ) of the L* value, a* value, and b* value were as follows: -Average L* value across all angles: 95.9 Average a* value for all angles: 4.2 Average b* value for all angles: -4.6 - Variation of L* value across all angles (3σ): 113.3 - Variation of a* value across all angles (3σ): 10.7 - Variation of b* value across all angles (3σ): 14.1
[0197] 1-4. Evaluation of rainbow unevenness Laminate 1 was produced in the same manner as in 1-3 above. In this case, the slow axis of the biaxially stretched plastic film of the optical film was arranged so as to be perpendicular to the absorption axis of the polarizer of the polarizing plate. The surface light source (liquid crystal display element) was set to display white in a darkroom environment, and the face was moved up and down and left and right from a distance of 30 cm to 100 cm away from laminate 1, and the laminate was visually observed from directions of ±90 degrees up and down and ±90 degrees left and right. The evaluators were healthy people in their 20s with eyesight of 0.7 or more, and evaluated the presence or absence of rainbow unevenness with the naked eye according to the following criteria. The above eyesight includes corrected eyesight. A: No rainbow unevenness is visible when viewed from any position or direction. B: Rainbow unevenness is visible in a small number of positions and / or directions in a very small area. C: There are many positions and / or directions in which rainbow unevenness is visible in a very small area. D: There are many positions and / or directions in which rainbow unevenness is visible in most areas.
[0198] 1-5.Evaluation of color distortion The laminate 1 was produced in the same manner as in 1-3 above. At that time, the slow axis of the biaxially stretched plastic film of the optical film was arranged so as to be perpendicular to the absorption axis of the polarizer of the polarizing plate. The surface light source (liquid crystal display element) was displayed in white in a darkroom environment, and the laminate 1 was observed once around the periphery with the elevation angle fixed at about (α+β) / 2. The observation can be said to be an observation at an azimuth angle of 0 to 359 degrees with the elevation angle fixed at about (α+β) / 2. The observation was carried out from a distance of 30 cm to 100 cm away from the laminate 1. The evaluator was a healthy person in his / her 20s with eyesight of 0.7 or more, and evaluated the presence or absence of color distortion with the naked eye according to the following criteria. The above eyesight includes corrected eyesight. A: The colours appear the same at all azimuth angles. B: There are a few azimuth angles where the colors appear different. C: There are many azimuth angles at which colors appear different. D: Colors appear different at most azimuth angles.
[0199] 1-6. Reflectance measurement A sample (5 cm x 5 cm) was prepared by bonding a black plate (KURARAY CO., LTD., product name "COMOGLAS DFA2CG 502K (Black) type", total light transmittance 0%, thickness 2 mm, refractive index 1.49) to the biaxially stretched plastic film side of the optical film of each of the examples and comparative examples via a 25 μm-thick transparent adhesive layer (PANAC CO., LTD., product name "Panaclean PD-S1", refractive index 1.49). When the direction perpendicular to the surface of the low refractive index layer side of the sample is set to 0 degrees, light is incident on the sample from a direction of 5 degrees, and the reflectance (visual reflectance Y value) is measured based on the regular reflection light of the incident light. The reflectance is measured by measuring the 5° regular reflectance in the wavelength range of 380 nm to 780 nm using a spectroscopic reflectance meter (Shimadzu Corporation, product name: MPC3100) and then calculating the value indicating the visual reflectance calculated by software (built-in MPC3100. Conditions for calculating reflectance: C light source, viewing angle 2 degrees) that converts it into the brightness perceived by the human eye. The reflectance was measured at 10 points for each sample, and the average value was taken as the reflectance of each sample.
[0200] 2. Fabrication and Preparation of Biaxially Stretched Polyester Films [Biaxially oriented polyester film 1] 1 kg of PET (melting point 258°C, absorption center wavelength: 320 nm) and 0.1 kg of ultraviolet absorber (2,2'-(1,4-phenylene)bis(4H-3,1-benzoxazinon-4-one) were melt-mixed at 280°C in a kneader to produce pellets containing the ultraviolet absorber. The pellets and PET with a melting point of 258°C were fed into a single-screw extruder and melt-kneaded at 280°C, extruded from a T-die, and cast onto a cast drum with a surface temperature controlled at 25°C to obtain a casting film. The amount of ultraviolet absorber in the casting film was 1 part by mass per 100 parts by mass of PET. The obtained casting film was heated with a group of rolls set at 95°C, and then stretched 3.3 times in the machine direction while heating both sides of the film with a radiation heater so that the film temperature at a point 250 mm into the 400 mm stretching section (starting point is stretching roll A and ending point is stretching roll B; stretching rolls A and B each have two nip rolls) would be 103°C, and then cooled once. During heating with the radiation heater, air at 92°C and 4 m / s was blown toward the film from the opposite side of the film from the radiation heater, generating turbulence on the front and back of the film and disrupting the temperature uniformity of the film. Next, both sides of this uniaxially stretched film were subjected to a corona discharge treatment in air to set the wetting tension of the base film to 55 mN / m, and the corona discharge-treated surfaces of both sides of the film were in-line coated with "a lubricity layer coating solution containing a polyester resin with a glass transition temperature of 18°C, a polyester resin with a glass transition temperature of 82°C, and silica particles with an average particle size of 100 nm" to form a lubricity layer. Next, the uniaxially stretched film was introduced into a tenter, preheated with hot air at 95 ° C., and then stretched 4.5 times in the film width direction at a temperature of 105 ° C. in the first stage and 140 ° C. in the second stage. Here, when the transverse stretching section was divided into two, the stretching amount of the film at the midpoint of the transverse stretching section (film width at the measurement point - film width before stretching) was stretched in two stages so that it was 80% of the stretching amount at the end of the transverse stretching section. The transversely stretched film was heat-treated in the tenter stepwise from 180 ° C. to 245 ° C. in the heat treatment temperature, followed by 1% relaxation treatment in the width direction under the same temperature conditions, and further quenched to 100 ° C., followed by 1% relaxation treatment in the width direction, and then wound up to obtain a biaxially stretched polyester film 1 (biaxially stretched polyester film used in Example 1) having a thickness of 40 μm.
[0201] [Biaxially oriented polyester film 2] As the biaxially stretched polyester film used in Comparative Example 1, a commercially available biaxially stretched polyester film (TOYOBO CO., LTD., product name: Cosmoshine A4100, thickness: 50 μm) was prepared.
[0202] [Biaxially oriented polyester film 3] Biaxially oriented polyester film 3 (biaxially oriented polyester film used in Example 2) having a thickness of 40 μm was obtained in the same manner as in the biaxially oriented polyester film 1, except that the stretching ratio in the width direction was changed from 4.5 times to 5.1 times.
[0203] [Biaxially oriented polyester film 4] Biaxially oriented polyester film 4 (biaxially oriented polyester film used in Example 3) was obtained in the same manner as for biaxially oriented polyester film 3, except that the thickness of the casting film of biaxially oriented polyester film 1 was increased and the final thickness was changed to 80 μm.
[0204] [Biaxially oriented polyester film 5] As the biaxially stretched polyester film used in Comparative Example 2, a commercially available biaxially stretched polyester film (Toray Industries, Inc., product name: 75U403, thickness: 75 μm) was prepared.
[0205] [Biaxially oriented polyester film 6] As the biaxially stretched polyester film used in Comparative Example 3, a commercially available biaxially stretched polyester film (TOYOBO CO., LTD., product name: Cosmoshine A4300, thickness: 23 μm) was prepared.
[0206] 3. Preparation of Optical Film [Example 1] A coating solution for forming a hard coat layer having the following formulation was applied onto the biaxially stretched polyester film 1 prepared in the above 2, and then dried at 70°C for 1 minute to volatilize the solvent. 2 ) to form a hard coat layer (dry thickness: 10 μm). A coating solution 1 for forming a low refractive index layer having the following formulation was applied onto the hard coat layer, and then dried at 60° C. for 1 minute to volatilize the solvent. 2 ) to form a low refractive index layer (dry thickness: 100 nm), and the optical film of Example 1 was obtained.
[0207] <Coating solution for forming hard coat layer> UV-curable acrylate-containing composition: 22 parts by weight (Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30", solid content 100%) UV-curable acrylate-containing composition: 17 parts by weight (Dai-ichi Kogyo Seiyaku Co., Ltd., product name "New Frontier R-1403MB (New Frontier R-1403M)", solid content 80%) Fluorine-based leveling agent: 1 part by weight (DIC Corporation, product name "MEGAFACE F-568") Photopolymerization initiator: 1 part by weight (IGM Resins BV, product name "Omnirad 184") Methyl isobutyl ketone: 15 parts by weight Methyl ethyl ketone: 44 parts by weight
[0208] <Coating liquid for forming low refractive index layer> UV-curable acrylate-containing composition: 1 part by weight (Nippon Kayaku Co., Ltd., product name "KAYARAD PET-30", solid content 100%) Photopolymerization initiator: 0.2 parts by weight (IGM Resins BV, product name "Omnirad 127") Hollow silica particles: 1.3 parts by weight (Average primary particle diameter 60nm) Solid silica particles: 0.7 parts by weight (Average primary particle diameter 15nm) Leveling agent: 0.1 parts by weight (Dainichiseika Color & Chemicals Mfg. Co., Ltd., product name "SEIKABEAM 10-28(MB)") ·Dilution solvent: 90 parts by mass (MIBK / AN=7 / 3)
[0209] [Examples 2 to 3] Optical films of Examples 2 and 3 were obtained in the same manner as in Example 1, except that the biaxially stretched polyester film 1 was changed to the biaxially stretched polyester films 3 and 4 prepared in the above "2".
[0210] [Comparative Example 1] An optical film of Comparative Example 1 was obtained in the same manner as in Example 1, except that the biaxially stretched polyester film 1 was changed to the biaxially stretched polyester film 2 prepared in the above "2".
[0211] [Comparative Examples 2 to 3] Optical films of Comparative Examples 2 and 3 were obtained in the same manner as in Example 1, except that the biaxially stretched polyester film 1 was changed to the biaxially stretched polyester films 5 and 6 prepared in the above "2".
[0212] [Reference example 1] The biaxially oriented polyester film 3 alone (the biaxially oriented polyester film 3 on which neither a hard coat layer nor a low refractive index layer was formed) was used as the optical film of Reference Example 1.
[0213] [Reference example 2] The biaxially oriented polyester film 2 alone (the biaxially oriented polyester film 2 on which neither a hard coat layer nor a low refractive index layer was formed) was used as the optical film of Reference Example 2.
[0214] [Reference example 3] A commercially available uniaxially stretched polyester film (TOYOBO CO., LTD., product name "Cosmoshine TA048", thickness: 80 μm) was used as the optical film of Reference Example 3.
[0215] [Table 1]
[0216] From the results in Table 1, it can be confirmed that the optical films of the examples in which the difference between the maximum and minimum values of ΔEab is less than 17.0 can suppress rainbow unevenness when viewed with the naked eye without increasing the in-plane retardation. Furthermore, from the results in Table 1, it can be confirmed that the optical films of the examples in which the difference between the maximum and minimum values of ΔEab is less than 17.0 can suppress color distortion. In contrast, it can be confirmed that the optical films of the comparative examples cannot suppress rainbow unevenness and color distortion, even though they have a low refractive index layer and have the same reflectance as the optical films of the examples. It can also be confirmed that the optical films of the examples are able to suppress the formation of bending creases or breakage after a bending test, regardless of the bending direction (the optical films of the examples are less likely to form bending creases or breakage compared to the uniaxially stretched polyester film (Reference Example 3) and the general biaxially stretched films (Comparative Examples 1 to 3)). It should be noted that the ΔEab in Table 1 is based on the measurement results at the central positions within the plane of Laminate 1 and Laminate 2, but similar results were obtained even when the measurement location was shifted (for example, the ΔEab at a location 130 mm to the left of the central position (other measurement location 1), a location 130 mm to the right of the central position (other measurement location 2), a location 75 mm above the central position (other measurement location 3), and a location 75 mm below the central position (other measurement location 4) were roughly equivalent to the values in Table 1). [Explanation of symbols]
[0217] 10: Plastic film 20: Hard coat layer 30: Low refractive index layer 100: Optical film 200: Surface light source 300: Polarizer 400: Adhesive layer 500: First transparent protective plate 600: Second transparent protective plate 700: Polarizing plate 800: Display element 1000: Image display device X: Laminate 1 Y: Laminate 2
Claims
1. An optical film having a low refractive index layer on a plastic film, The plastic film is a biaxially stretched plastic film having an in-plane retardation of 2500 nm or less, the low refractive index layer is located on the outermost surface of the optical film, An optical film having a region in which the difference between the maximum and minimum values of ΔEab is less than 17.
0. Here, measurement 1 is carried out for laminate 1 to calculate the L*, a*, and b* values in the L*a*b* color system. Measurement 2 is carried out for laminate 2 to calculate the L*, a*, and b* values in the L*a*b* color system. Based on the results of measurements 1 and 2, ΔEab is calculated under condition 1. <Measurement 1> A laminate 1 is prepared by laminating a polarizer and the optical film in this order on a surface light source. In the laminate 1, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is also arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the surface light source is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees. The surface light source of the laminate 1 is displayed as white, and the transmitted light emitted from the low refractive index layer side of the laminate 1 is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is an arbitrary 1 mm 2 More than 10mm 2 The areas are as follows: <Measurement 2> A laminate 2 is prepared by laminating a polarizer on the same surface light source as in the measurement 1. The polarizer is arranged so that the direction of the absorption axis with respect to the surface light source is the same as in the measurement 1. The surface light source of the laminate 2 is displayed as white, and the transmitted light emitted from the polarizer side of the laminate 2 is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to be approximately the same as that of measurement 1 within the plane. <Condition 1> For all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2 from the L* value of measurement 1. ΔL* is grayscaled from the maximum value to the minimum value in a predetermined gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angles are represented by concentric circles and the azimuth angles are represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. With respect to the elevation angles located at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L* value, a* value, and b* value of measurement 1 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2, and the L* value, a* value, and b* value of measurement 2 at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2.
2. An optical film as described in claim 1, wherein the plastic film is a biaxially stretched plastic film having an in-plane phase difference relative to the phase difference in the thickness direction of 0.10 or less.
3. An optical film as described in claim 1 or 2, having one or more layers selected from a hard coat layer, an anti-glare layer and a high refractive index layer between the plastic film and the low refractive index layer.
4. An optical film described in any one of claims 1 to 3, wherein the thickness of the plastic film is 15 μm or more and 200 μm or less.
5. An optical film described in any one of claims 1 to 4, wherein the plastic film is a biaxially oriented polyester film.
6. A polarizing plate having a polarizer, a first transparent protective plate arranged on one side of the polarizer, and a second transparent protective plate arranged on the other side of the polarizer, wherein at least one of the first transparent protective plate and the second transparent protective plate is an optical film described in any one of claims 1 to 5.
7. An image display device having a display element, and a polarizer and an optical film arranged on the light output surface side of the display element, wherein the optical film is an optical film described in any one of claims 1 to 5, and is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees, and the surface of the optical film on the low refractive index layer side faces the opposite side to the display element.
8. An image display device comprising a polarizer and an optical film on a light exit surface of a display element, the polarizer is disposed such that an angle formed between a direction of an absorption axis of the polarizer and a left-right direction or a up-down direction of the display element is within ±5 degrees; the polarizer and the biaxially stretched plastic film of the optical film are disposed such that an angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ± 5 degrees; The optical film has a low refractive index layer on a biaxially stretched plastic film having an in-plane retardation of less than 2500 nm, the low refractive index layer is located on the outermost surface of the optical film, and the image display device has a region in which the difference between the maximum and minimum values of ΔEab is less than 17.
0. Here, measurement 1A is carried out for laminate 1A to calculate the L*, a*, and b* values in the L*a*b* color system. Measurement 2A is carried out for laminate 2A to calculate the L*, a*, and b* values in the L*a*b* color system. Based on the results of measurements 1A and 2A, ΔEab is calculated under condition 1A. <Measurement 1A> A laminate 1A is prepared by laminating a polarizer and the optical film in this order on a display element. In the laminate 1A, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. Furthermore, the absorption axis of the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film is within 90 degrees ±5 degrees. The display element of the laminate 1A is set to display white, and the transmitted light exiting from the low refractive index layer side of the laminate 1A is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area for the transmitted light is an arbitrary area within the plane of 1 to 10 mm2. <Measurement 2A> A laminate 2A was prepared by laminating a polarizer on the same display element as in the measurement 1A. The display element of the laminate 2A is set to display white, and the transmitted light emitted from the polarizer side of the laminate 2A is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to be approximately the same as that of measurement 1A within the plane. <Condition 1A> At all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2A from the L* value of measurement 1A. ΔL* is grayscaled from the maximum value to the minimum value in a predetermined gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angles are represented by concentric circles and the azimuth angles are represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. With respect to the elevation angles located at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L* value, a* value, and b* value of measurement 1A at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2, and the L* value, a* value, and b* value of measurement 2A at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2.
9. A method for selecting an optical film for an image display device, the method comprising the steps of: having a polarizer and an optical film on a light-emitting surface of a display element; and arranging the polarizer so that the direction of the absorption axis is parallel to the left-right direction or the up-down direction of the display element, the method comprising the steps of: A method for selecting an optical film for an image display device, comprising the steps of: an optical film X having a low refractive index layer on a biaxially stretched plastic film having an in-plane retardation of less than 2500 nm, the low refractive index layer being located on the outermost surface of the optical film X; and the optical film X having a region in which a difference between a maximum value and a minimum value of ΔEab is less than 17.0; and selecting an optical film X that satisfies the judgment condition as the optical film. Here, measurement 1B is carried out for laminate 1B to calculate the L*, a*, and b* values of the L*a*b* color system. Measurement 2B is carried out for laminate 2B to calculate the L*, a*, and b* values of the L*a*b* color system. Based on the results of measurements 1B and 2B, ΔEab is calculated under condition 1B. <Measurement 1B> A laminate 1B is prepared by laminating a polarizer and the optical film X in this order on a display element. In the laminate 1B, the optical film is arranged so that the surface on the low refractive index layer side faces the opposite side to the polarizer. The polarizer is also arranged so that the angle between the absorption axis of the polarizer and the left-right direction or the up-down direction of the display element is within ±5 degrees. Furthermore, the polarizer is arranged so that the angle between the absorption axis of the polarizer and the slow axis of the biaxially stretched plastic film of the optical film X is within 90 degrees ±5 degrees. The display element of the laminate 1B is set to display white, and the transmitted light exiting from the low refractive index layer side of the laminate 1B is measured at an elevation angle of 0 to 80 degrees and an azimuth angle of 0 to 359 degrees, one degree at a time, and the L*, a*, and b* values of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area for the transmitted light is an arbitrary area within the plane of 1 to 10 mm2. <Measurement 2B> A laminate 2B was prepared by laminating a polarizer on the same display element as in the measurement 1B. The display element of the laminate 2B is set to display white, and the transmitted light emitted from the polarizer side of the laminate 2B is measured at an elevation angle of 0 degrees or more and 80 degrees or less and an azimuth angle of 0 degrees or more and 359 degrees or less, one degree at a time, and the L* value, a* value, and b* value of the L*a*b* color system are calculated based on the transmitted light at each angle. The measurement area of the transmitted light is set to be approximately the same as that of measurement 1B within the plane. <Condition 1B> For all elevation angles and all azimuth angles, ΔL* is calculated by subtracting the L* value of measurement 2B from the L* value of measurement 1B. ΔL* is grayscaled from the maximum value to the minimum value in a predetermined gradation, and displayed in grayscale on a two-dimensional coordinate system in which the elevation angles are represented by concentric circles and the azimuth angles are represented by vertical and horizontal lines. It is confirmed that there are two regions in which ΔL* is distributed concentrically in the two-dimensional coordinate system, and that the two regions are located at approximately symmetrical positions in the two-dimensional coordinate system. With respect to the elevation angles at the center of the region in which ΔL* is distributed concentrically, one elevation angle is set to α degrees and the other elevation angle is set to β degrees. ΔEab at each azimuth angle is calculated from the difference between the L* value, a* value, and b* value of measurement 1B at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2, and the L* value, a* value, and b* value of measurement 2B at an azimuth angle of 0 degrees or more and 359 degrees or less when the elevation angle is (α + β) / 2.